Polyimide film, polyimide varnish, method for producing polyimide film, laminate, display member, touch panel member, liquid crystal display device, and organic electroluminescence display device

A polyimide film with specific structural units and molecular weight, produced using a dichloromethane-based varnish, addresses bubble defects and enhances bending resistance, suitable for flexible displays.

JP7608731B2Active Publication Date: 2025-01-07DAI NIPPON PRINTING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020097233
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-17
Filing Date
2020-06-03
Publication Date
2025-01-07
Estimated Expiration
2040-06-03

AI Technical Summary

Technical Problem

Resin films used as glass substitutes in flexible displays are prone to air bubble defects and lack sufficient bending resistance, making them unsuitable for repeated bending without causing display defects.

Method used

A polyimide film containing specific structural units and a weight average molecular weight of 100,000 to 270,000, produced using a polyimide varnish with a high dichloromethane content, is applied and heated to minimize bubble defects and enhance bending resistance.

Benefits of technology

The polyimide film achieves reduced bubble defects and improved bending resistance, ensuring uniform thickness and flexibility for use in flexible displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608731000027
    Figure 0007608731000027
  • Figure 0007608731000028
    Figure 0007608731000028
  • Figure 0007608731000029
    Figure 0007608731000029
Patent Text Reader

Abstract

To provide a polyimide film having good film thickness uniformity and appearance and good flexure resistance.SOLUTION: The polyimide film comprises a polyimide having a structural unit represented by formula (1) by 10 mol% or more and 100 mol% or less and a structural unit represented by formula (2) by (100-x) mol% (where x represents the mol% of the structural unit represented by formula (1)), and has a weight average molecular weight of 100,000 or more and 270,000 or less in terms of polystyrene by gel permeation chromatography.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide film, a polyimide varnish, a method for producing a polyimide film, a laminate, a display member, a touch panel member, a liquid crystal display device, and an organic electroluminescence display device. [Background technology]

[0002] Although thin plate glass has excellent hardness and heat resistance, it has some disadvantages, such as being difficult to bend, easily breaking when dropped, having problems with workability, and being heavy compared to plastic products. For this reason, in recent years, resin products such as resin substrates and resin films have been replacing glass products in terms of workability and weight reduction, and research into resin products that can replace glass has been conducted.

[0003] For example, with the rapid progress of electronics such as liquid crystal and organic electroluminescence displays and touch panels, there is a demand for devices to be thinner, lighter, and more flexible. Conventionally, these devices have various electronic elements, such as thin transistors and transparent electrodes, formed on thin plate glass, but by replacing this thin plate glass with a resin film, the impact resistance of the panel itself can be strengthened and it can be made more flexible, thinner, and lighter.

[0004] Generally, polyimide is a highly heat-resistant resin obtained by dehydration ring-closing reaction of polyamic acid obtained by condensation reaction of aromatic tetracarboxylic anhydride and aromatic diamine. However, polyimide generally shows yellow or brown coloration, so it has been difficult to use it in fields requiring transparency such as display applications and optical applications. Therefore, application of polyimide with improved transparency to display members has been considered. For example, Patent Document 1 discloses a polyimide resin having high heat resistance, high transparency, and low water absorption, which is obtained by reacting at least one acyl-containing compound selected from the group consisting of 1,2,4,5-cyclohexanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and reactive derivatives thereof with at least one imino-forming compound selected from compounds having at least one phenylene group and isopropylidene group represented by a specific formula, and describes that it is suitable for substrate materials such as flat panel displays and mobile phone devices.

[0005] Furthermore, Patent Document 2 discloses a transparent polyimide film that contains a unit structure derived from an aromatic dianhydride and an aromatic diamine, and further contains a unit structure derived from a tear strength improving additive or a monomer having a functional group selected from the group consisting of a hexafluoro group, a sulfone group, and an oxy group.

[0006] Patent Document 3 also discloses a polyimide having excellent transparency, high heat resistance, a low coefficient of linear thermal expansion, and solvent processability with a low hygroscopic solvent, which is obtained by reacting a tetracarboxylic dianhydride obtained by esterifying trimellitic anhydride chloride with 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with 2,2-bis(trifluoromethyl)benzidine to obtain a polyamic acid, and then imidizing the obtained polyamic acid. It is described that the polyimide in Patent Document 3 simultaneously achieves low thermal expansion properties, solvent solubility, and high transparency by introducing a parabiphenylene group with a large twisted dihedral angle via an ester bond in order to increase solvent solubility while making the main chain skeleton as linear and rigid as possible. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2006-199945 A [Patent Document 2] Special Publication No. 2014-501301 [Patent Document 3] International Publication No. 2014 / 046180 Summary of the Invention [Problem to be solved by the invention]

[0008] Resin products that can serve as glass substitutes are required to have a uniform thickness and a good appearance, such as the absence of air bubbles, when made into a film of a desired thickness that can function as a glass substitute. In addition, mobile devices with foldable screens are folded when carried and unfolded when used. Therefore, flexible displays mounted on mobile devices are required to be able to withstand repeated bending without causing display defects, and the base and surface materials for flexible displays are required to have bending resistance when repeatedly bent (hereinafter sometimes referred to as dynamic bending resistance). However, the polyimide film described in Patent Document 3 has a thin thickness, and when a film having a desired thickness capable of functioning as a glass substitute is produced by the polyimide film manufacturing method described in Patent Document 3, there is a problem that air bubbles are generated in the film. A polyimide film having air bubbles in the film is deemed to have air bubble defects and cannot be used as a glass substitute. At the same time, there is a demand for the polyimide film to have good bending resistance.

[0009] The present invention has been made in consideration of the above problems, and has as its main object to provide a polyimide film which is less susceptible to bubble defects and has good bending resistance. Another object of the present invention is to provide a polyimide varnish for producing the polyimide film, a method for producing the polyimide film, a laminate having the polyimide film, a display member which is the polyimide film or the laminate, and a touch panel member, a liquid crystal display device, and an organic electroluminescence display device which include the polyimide film or the laminate. [Means for solving the problem]

[0010] The present invention provides a polyimide film containing a polyimide that contains 10 mol % or more and 100 mol % or less of a structural unit represented by the following general formula (1) and (100-x) mol % (wherein x is the mol % of the structural unit represented by the general formula (1)) of a structural unit represented by the following general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less, as calculated using polystyrene standards by gel permeation chromatography:

[0011] [ka] (In general formulas (1) and (2), R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 1 and R 2 At least one of, and R 3and R 4 At least one of A represents an alkyl group having 1 to 6 carbon atoms, A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring.

[0012] The present invention also provides a polyimide varnish containing a polyimide and an organic solvent, The polyimide contains 10 mol % or more and 100 mol % or less of the constitutional unit represented by the general formula (1) and (100-x) mol % (wherein x is the mol % of the constitutional unit represented by the general formula (1)) of the constitutional unit represented by the general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less as calculated on a polystyrene basis by gel permeation chromatography; The organic solvent contains dichloromethane in an amount of 90% by mass or more based on the total amount of the organic solvent. The polyimide varnish is provided, wherein the content of the polyimide in the polyimide varnish is 6% by mass or more and 15% by mass or less.

[0013] The polyimide film of the present invention preferably contains dichloromethane in an amount of 1 ppm to 2000 ppm, since even if the film has a thickness of 30 μm or more, the film has good thickness uniformity and appearance, and has improved bending resistance.

[0014] In the polyimide film and polyimide varnish of the present invention, the diamine residue having an aromatic ring or an aliphatic ring in B in the general formulas (1) and (2) of the polyimide is a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, a 3,3'-bis(trifluoromethyl)-4,4'-[(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)bis(4,1-phenyleneoxy)]dianiline residue, a 2,2-bis[3-(3-aminophenoxy) From the viewpoints of light transmittance, bending resistance, and surface hardness, it is preferable that the divalent group contains at least one selected from the group consisting of an N,N'-bis(4-aminophenyl)terephthalamide residue, a 4-aminophenyl-4-aminobenzoate residue, a (2-phenyl-4-aminophenyl)-4-aminobenzoate residue, and a bis(4-aminophenyl)terephthalate residue:

[0015] [ka] (In the general formula (3), R 5 and R 6 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.

[0016] In the polyimide film and polyimide varnish of the present invention, the tetracarboxylic acid residue having an aromatic ring or an aliphatic ring in A in the general formula (2) of the polyimide is a cyclohexanetetracarboxylic acid dianhydride residue, a cyclopentanetetracarboxylic acid dianhydride residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid dianhydride residue, a cyclobutanetetracarboxylic acid dianhydride residue, a pyromellitic acid dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic acid dianhydride residue, a 2,2',3,3'-biphenyltetracarboxylic acid dianhydride residue, a ... In terms of light transmittance, bending resistance, and surface hardness, the phthalic anhydride residue is preferably at least one tetravalent group selected from the group consisting of tetrafluoroethylene diphthalic anhydride residue, 2,3,3',4'-biphenyltetracarboxylic dianhydride residue, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride residue, 4,4'-oxydiphthalic anhydride residue, and 3,4'-oxydiphthalic anhydride residue.

[0017] The present invention also relates to a method for producing a polyimide varnish according to the present invention, the polyimide varnish having a viscosity of 1,000 to 10,000 cps at 25°C as measured by a rotational viscometer; applying the polyimide varnish to a substrate, drying the polyimide varnish at a temperature of 40° C. or less, and peeling the coating film from the substrate after drying; The present invention provides a method for producing a polyimide film, comprising a step of fixing the ends of the dried coating film peeled from the support, and then heating the dried coating film at a temperature of 150° C. or higher.

[0018] The present invention also provides a laminate comprising the polyimide film of the present invention and a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound. The present invention also provides a laminate comprising a glass substrate having a thickness of 100 μm or less and the polyimide film of the present invention. The present invention also provides a laminate having, in this order, a glass substrate having a thickness of 100 μm or less, the polyimide film of the present invention, and a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound.

[0019] The present invention also provides a display member which is the polyimide film of the present invention or the laminate of the present invention. The display member can be used for a flexible display.

[0020] The present invention also relates to a polyimide film or a laminate of the present invention, a transparent electrode including a plurality of conductive portions disposed on one surface side of the polyimide film or the laminate; and a plurality of lead wires electrically connected to at least one side of an end of the conductive portion.

[0021] The present invention also relates to a polyimide film or a laminate of the present invention, and a liquid crystal display section disposed on one surface side of the polyimide film or the laminate and having a liquid crystal layer between opposing substrates.

[0022] The present invention also relates to a polyimide film or a laminate of the present invention, and an organic electroluminescence display section disposed on one surface side of the polyimide film or the laminate and having an organic electroluminescence layer between opposing substrates. Effect of the Invention

[0023] According to the present invention, it is possible to provide a polyimide film which is less susceptible to bubble defects and has good bending resistance. According to the present invention, it is possible to provide a method for producing a polyimide film which is less susceptible to bubble defects, has good film thickness uniformity, and has good bending resistance. The present invention can also provide a polyimide varnish for producing the polyimide film, a laminate having the polyimide film, a display member which is the polyimide film or the laminate, and a touch panel member, a liquid crystal display device, and an organic electroluminescence display device each including the polyimide film or the laminate. [Brief description of the drawings]

[0024] [Figure 1] FIG. 13 is a diagram for explaining a method of a static bending test. [Diagram 2] FIG. 1 is a diagram for explaining a method of a dynamic bending test. [Diagram 3] 1 is a schematic plan view of one surface of an example of a touch panel member of the present invention. [Figure 4] 4 is a schematic plan view of the other surface of the touch panel member shown in FIG. 3. [Diagram 5] 5 is a cross-sectional view taken along line AA' of the touch panel member shown in FIGS. 3 and 4. FIG. [Figure 6] 1 is a schematic plan view showing an example of a conductive member including a laminate of the present invention. [Figure 7] FIG. 2 is a schematic plan view showing another example of a conductive member including a laminate of the present invention. [Figure 8] FIG. 4 is a schematic cross-sectional view showing another example of the touch panel member of the present invention. [Figure 9] FIG. 1 is a schematic cross-sectional view showing an example of a liquid crystal display device of the present invention. [Figure 10] FIG. 4 is a schematic cross-sectional view showing another example of a liquid crystal display device of the present invention. [Figure 11] 1 is a schematic cross-sectional view showing an example of an organic electroluminescence display device of the present invention. [Figure 12] FIG. 2 is a schematic cross-sectional view showing another example of an organic electroluminescence display device of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The polyimide film according to the present invention, a polyimide varnish for producing the polyimide film, a method for producing the polyimide film, a laminate using the polyimide film, a display member, a touch panel member, a liquid crystal display device, and an organic electroluminescence display device will be described in detail below. In addition, terms used in this specification that specify shapes, geometric conditions, and the degree thereof, such as "parallel," "orthogonal," and "same," as well as values ​​of length and angle, are not to be bound by strict meanings, but are to be interpreted to include a range within which similar functions can be expected. In this specification, when describing a mode in which another component is disposed on a certain component, the term "above" or "below" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween. Also, in this specification, when describing a mode in which another component is disposed on the surface of a certain component, the term "on the surface side" or "on the surface" is used, unless otherwise specified, to include both a case in which another component is disposed directly above or below a certain component so as to be in contact with the component, and a case in which another component is disposed above or below a certain component with another component interposed therebetween. In addition, in this specification, (meth)acrylic means both acrylic and methacrylic. In addition, in this specification, "light" means actinic rays or radiation, and includes, for example, the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light (EUV light), X-rays, electron beams, and the like. In addition, in the drawings attached to this specification, the scale and the aspect ratio may be appropriately changed and exaggerated from those of the actual objects for the convenience of illustration and ease of understanding. In addition, in this specification, the use of "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, the unit of "ppm" used to express the content of an organic solvent in a polyimide film represents ppm by mass.

[0026] I. Polyimide film The polyimide film of the present invention is a polyimide film containing 10 mol % or more and 100 mol % or less of a structural unit represented by the following general formula (1) and (100-x) mol % (wherein x is the mol % of the structural unit represented by the general formula (1)) of a structural unit represented by the following general formula (2), and containing a polyimide having a weight average molecular weight of 100,000 or more and 270,000 or less as calculated in terms of polystyrene by gel permeation chromatography:

[0027] [ka] (In general formulas (1) and (2), R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 1 and R 2 At least one of, and R 3 and R 4 At least one of A represents an alkyl group having 1 to 6 carbon atoms, A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring.

[0028] According to the present invention, the polyimide contained in the polyimide film is selected to have a predetermined amount or more of tetracarboxylic acid residues having a specific structure including a parabiphenylene group with a twisted dihedral angle via an ester bond in the main chain, and a diamine residue having an aromatic ring or an aliphatic ring, and to have a specific weight-average molecular weight, so that a polyimide film that is less likely to develop air bubble defects in the film and has good bending resistance can be provided. When the structural unit represented by the following general formula (1) is contained in an amount of 10 mol % or more, a film having a high elastic modulus can be obtained while maintaining solubility in a solvent.

[0029] In the polyimide films having similar film thicknesses in the Examples and Comparative Examples described below, even if polyimides having the same molecular structure are used, if the weight-average molecular weight is lower than a certain level, the dynamic bending resistance is poor, and if the weight-average molecular weight is higher than a certain level, the viscosity of the polyimide varnish increases, the defoaming ability from the coating film becomes poor, air bubbles are generated in the film, and the polyimide film cannot be used as a product.

[0030] The polyimide film according to the present invention will be described in detail below. The polyimide film according to the present invention contains polyimide, and may further contain other components or have other structures as long as the effects of the present invention are not impaired. 1. Polyimide Polyimide is obtained by reacting a tetracarboxylic acid component with a diamine component. It is preferable to obtain a polyamic acid by polymerization of the tetracarboxylic acid component and the diamine component, and then imidize the polyamic acid. The imidization may be performed by chemical imidization, thermal imidization, or a combination of chemical imidization and thermal imidization. The polyimide used in the present invention contains 10 mol % or more and 100 mol % or less of constitutional units represented by the following general formula (1) and (100-x) mol % (wherein x is the mol % of the constitutional units represented by the general formula (1)) of constitutional units represented by the following general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less as calculated using polystyrene standards by gel permeation chromatography.

[0031] [ka] (In general formulas (1) and (2), R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 1 and R 2 At least one of, and R 3 and R 4At least one of A represents an alkyl group having 1 to 6 carbon atoms, A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring.

[0032] Here, the tetracarboxylic acid residue refers to a residue obtained by removing four carboxyl groups from a tetracarboxylic acid, and has the same structure as the residue obtained by removing the acid dianhydride structure from a tetracarboxylic dianhydride. Moreover, the diamine residue refers to a residue obtained by removing two amino groups from a diamine.

[0033] In the general formula (1), R 1 and R 2 At least one of, and R 3 and R 4 At least one of these represents an alkyl group having 1 to 6 carbon atoms. The alkyl group having 1 to 6 carbon atoms may be a linear or branched alkyl group, and examples thereof include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, a t-butyl group, an n-pentyl group, and an n-hexyl group. From the viewpoint of solvent solubility, an alkyl group having 1 to 4 carbon atoms is preferable, an alkyl group having 1 to 2 carbon atoms is more preferable, and a methyl group is more preferable. Among others, R 1 and R 2 , and R 3 and R 4 However, it is preferable that the aryl group represents a methyl group from the viewpoint of solubility in a solvent.

[0034] In general formula (1), B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring. The diamine residue having an aromatic ring or an aliphatic ring can be a residue obtained by removing two amino groups from a diamine having an aromatic ring or a diamine having an aliphatic ring. The diamine residue having an aromatic ring or an aliphatic ring may have at least an aromatic ring or an aliphatic ring, and may have both an aromatic ring and an aliphatic ring. Examples of diamines having an aromatic ring include p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4, 4'-Diaminobenzophenone, 3,4'-Diaminobenzophenone, 4,4'-Diaminobenzanilide, 3,3'-Diaminodiphenylmethane, 4,4'-Diaminodiphenylmethane, 3,4'-Diaminodiphenylmethane, 2,2-Di(3-aminophenyl)propane, 2,2-Di(4-aminophenyl)propane, 2-(3-aminophenyl)-2-(4-aminophenyl)propane, 2,2-Di(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-Di(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane Fluoropropane, 2-(3-aminophenyl)-2-(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 1,1-di(3-aminophenyl)-1-phenylethane, 1,1-di(4-aminophenyl)-1-phenylethane, 1-(3-aminophenyl)-1-(4-aminophenyl)-1-phenylethane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis bis(3-aminobenzoyl)benzene, 1,3-bis(4-aminobenzoyl)benzene, 1,4-bis(3-aminobenzoyl)benzene, 1,4-bis(4-aminobenzoyl)benzene, 1,3-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,3-bis(4-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(3-amino-α,α-dimethylbenzyl)benzene, 1,4-bis(4-amino-α,α-dimethylbenzyl)benzene, 1,3-bis(3-amino-α,α-ditrifluoromethylbenzyl)benzene, 1,3-Bis(4-amino-α,α-ditrifluoromethylbenzyl)benzene, 1,4-bis(3-amino-α,α-ditrifluoromethylbenzyl)benzene, 1,4-bis(4-amino-α,α-ditrifluoromethylbenzyl)benzene, 2,6-bis(3-aminophenoxy)benzonitrile, 2,6-bis(3-aminophenoxy)pyridine, N,N'-bis(4-aminophenyl)terephthalamide, 4-aminophenyl-4-aminobenzoate, (2-phenyl-4-aminophenyl)-4-aminobenzoate, bis(4-aminophenyl terephthalate, 9,9-bis(4-aminophenyl)fluorene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (2,2-bis(trifluoromethyl)benzidine), 3,3'-dichloro-4,4'-diaminobiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(3-amino 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4 ... 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 1,4-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(3-aminophenoxy)-α,α-dimethylbenzyl]benzene, 1,4-bis[4-(4-aminophenoxy)-α,α-dimethylbenzyl]benzene, 4,4'-bis[4-(4-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, 4,4'-bis[4-(4-aminophenoxy)phenoxy]diphenyl Sulfone, 3,3'-diamino-4,4'-diphenoxybenzophenone, 3,3'-diamino-4,4'-diviphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 3,3'-diamino-4-biphenoxybenzophenone, 6,6'-bis(3-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 6,6'-bis(4-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane, and the like, and diamines in which some or all of the hydrogen atoms on the aromatic ring of the diamine are substituted with a substituent selected from a fluoro group, a methyl group, a methoxy group, a trifluoromethyl group, or a trifluoromethoxy group can also be used.

[0035] The diamine residue having an aromatic ring preferably contains a diamine residue of a diamine represented by the following general formula (5), including the above-mentioned N,N'-bis(4-aminophenyl)terephthalamide, 4-aminophenyl-4-aminobenzoate, (2-phenyl-4-aminophenyl)-4-aminobenzoate, and bis(4-aminophenyl)terephthalate, from the viewpoint of improving the elastic modulus. By introducing a diamine residue in which two or three phenylene groups are bonded by at least one of an amide bond and an ester bond, the planarity of the molecular chain can be increased, promoting π-π intermolecular interactions between the molecular chains, and further, when an amide bond is contained, the intermolecular force due to the formation of hydrogen bonds between the amide bond site and the ester bond site of the tetracarboxylic acid residue of general formula (1) can be increased, which is considered to improve the elastic modulus.

[0036] [ka] (In formula (5), R 7 each independently represents a halogenated alkyl group, an alkyl group, a cycloalkyl group, or an aryl group; Z 1 and Z 2 each independently represents a divalent group selected from the group consisting of -NHCO-, -CONH-, -OCO-, and -COO-; Z 2 is bonded to the para or meta position relative to the amino group, and Z 1 is Z 2 is bonded to the para or meta position relative to the

[0037] In formula (5), R 7each independently represents a halogenated alkyl group, an alkyl group, a cycloalkyl group, or an aryl group. The alkyl group includes an alkyl group having 1 to 10 carbon atoms, and preferably an alkyl group having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, and a propyl group. The halogenated alkyl group includes an alkyl group having 1 to 10 carbon atoms, and preferably an alkyl group having 1 to 3 carbon atoms, such as a trifluoromethyl group, a tetrafluoroethyl group, a heptafluoropropyl group, a monofluoromethyl group, and a difluoromethyl group. The cycloalkyl group includes a cycloalkyl group having 5 to 7 carbon atoms, such as a cyclopentyl group, a cyclohexyl group, and a cycloheptyl group. The aryl group includes an aryl group having 6 to 12 carbon atoms, and preferably an aryl group having 6 to 10 carbon atoms, such as a phenyl group, a naphthyl group, and a biphenyl group.

[0038] R 7 As the group, a halogenated alkyl group is preferably used from the viewpoint of transparency, an alkyl group is preferably used from the viewpoint of imparting solubility in a solvent, a cycloalkyl group is preferably used from the viewpoint of imparting solubility without impairing the planarity of the molecular chain, and an aryl group is preferably used from the viewpoint of increasing the planarity and rigidity of the molecular chain and improving the elastic modulus.

[0039] Substituent R 7 Each of j1, j2, and j3, which indicate the number of, independently represents an integer of 0 to 4. Each of j1, j2, and j3 is preferably an integer of 0 to 2, and more preferably an integer of 0 to 1. Furthermore, j1+j2+j3 is preferably an integer of 0 to 6, and more preferably an integer of 0 to 3.

[0040] k represents an integer of 0 or 1, and when k is 0, two phenylene groups are linked together. When k is 0, it is preferable that at least one of j1 and j2 represents an integer of 1 or more in order to obtain the effect of the substituent. That is, when k is 0, the substituent R 7 It is preferable that at least one of the following is contained in the diamine residue. When k is 0, j1+j2 is preferably 1 to 4, and more preferably 1 or 2. Substituent R when k is 0 7 may be appropriately selected from the above viewpoints, but from the viewpoints of increasing the planarity and rigidity of the molecular chain, an aryl group is preferably used, and it is preferable for the copolymer to contain at least one aryl group.

[0041] Z 1 and Z 2 each independently represents a divalent group selected from the group consisting of -NHCO-, -CONH-, -OCO-, and -COO-; Z 2 is bonded to the para or meta position relative to the amino group, and Z 1 is Z 2 It bonds to the para or meta position. In terms of increasing reactivity by bonding the aromatic ring directly connected to the raw diamine with -NH- and making the aromatic ring electron-rich, when k=0, Z 1 is preferably -NHCO- or -CONH-, and when k=1, Z 2 is -NHCO-, Z 1 is more preferably -CONH-. In addition, in order to increase the reactivity of the aromatic ring by bonding it to the aromatic ring directly connected to the diamine of the raw material with -O-, and making the aromatic ring electron-rich, when k=0, Z 1 is preferably -OCO- or -COO-, and when k=1, Z 2 is -OCO-, Z 1 is more preferably -COO-. In addition, by making the main structure of the molecular chain linear and facilitating stacking, it is possible to increase the elastic modulus. 2 is attached at the para position to the amino group, and Z 1 is Z 2 It is preferred that the bond be para to the

[0042] Examples of the diamine represented by the formula (5) include, but are not limited to, diamines having the following structures:

[0043] [ka]

[0044] [ka]

[0045] [ka]

[0046] [ka]

[0047] The diamine residue of the structural unit represented by the formula (5) may be a diamine residue of at least one diamine selected from the group consisting of the formulae (DA1), (DA4), (DA7), and (DA29) since it is necessary to select a highly reactive diamine in order to obtain a high molecular weight polymer.

[0048] Examples of diamines having an aliphatic ring include 1,4-cyclohexanediamine, trans-1,4-bismethylenecyclohexanediamine, 2,6-bis(aminomethyl)bicyclo[2,2,1]heptane, and 2,5-bis(aminomethyl)bicyclo[2,2,1]heptane. The diamine residue having an aromatic ring or an aliphatic ring may be used alone or in combination of two or more kinds.

[0049] The polyimide used in the present invention contains the constitutional unit represented by the general formula (2) at (100-x) mol % (where x is the mol % of the constitutional unit represented by the general formula (1)). When the polyimide used in the present invention contains the constitutional unit represented by the general formula (1) at 100 mol %, the constitutional unit represented by the general formula (2) is 0 mol %, i.e., no constitutional unit is contained.

[0050] In the general formula (2), A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring. Since B in the general formula (2) may be the same as B in the general formula (1), the explanation here is omitted. B in the general formula (1) and B in the general formula (2) may be the same or different.

[0051] The tetracarboxylic acid residue in A of the general formula (2) can be a residue obtained by removing an acid dianhydride structure from a tetracarboxylic acid dianhydride having an aromatic ring, or a residue obtained by removing an acid dianhydride structure from a tetracarboxylic acid dianhydride having an aliphatic ring. Examples of tetracarboxylic dianhydrides having an aromatic ring include pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride residue, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, and the like. 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, Anhydride, 1,3-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 1,4-bis[(3,4-dicarboxy)benzoyl]benzene dianhydride, 2,2-bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, 2,2-bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}propane dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, 4,4 '-Bis[4-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, 4,4'-bis[3-(1,2-dicarboxy)phenoxy]biphenyl dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}ketone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfone dianhydride, bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, bis{4-[3-(1,2-dicarboxy)phenoxy]phenyl}sulfide dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,4'-oxydiphthalic acid Examples of the dianhydride include 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, and 1,2,7,8-phenanthrenetetracarboxylic dianhydride. Examples of tetracarboxylic dianhydrides having an aliphatic ring include cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic dianhydride, dicyclohexane-3,4,3',4'-tetracarboxylic dianhydride, and cyclobutanetetracarboxylic dianhydride. These may be used alone or in combination of two or more.

[0052] The polyimide film used in the present invention contains 10 mol % or more and 100 mol % or less of the constitutional unit represented by the general formula (1). From the viewpoint of solubility in a solvent, the polyimide film used in the present invention preferably contains 15 mol % or more of the structural unit represented by the general formula (1), more preferably 25 mol % or more, even more preferably 50 mol % or more, and even more preferably 60 mol % or more. On the other hand, in order to improve surface hardness and light transmittance, a copolymerization component may be contained, and the polyimide film used in the present invention may contain 95 mol % or less of the structural unit represented by the general formula (1), further may contain 90 mol % or less, and further may contain 80 mol % or less.

[0053] The polyimide film used in the present invention contains the constitutional unit represented by the general formula (2) in an amount of (100-x) mol % (where x is the mol % of the constitutional unit represented by the general formula (1)). From the viewpoint of solubility in a solvent, in the polyimide film used in the present invention, the structural unit represented by the general formula (2) is preferably 85 mol % or less, more preferably 75 mol % or less, even more preferably 50 mol % or less, and even more preferably 40 mol % or less. In the polyimide film used in the present invention, the structural unit represented by the general formula (2) may be 0 mol %, but may be contained as a copolymerization component from the viewpoint of improving surface hardness and light transmittance. The polyimide film used in the present invention may contain the structural unit represented by the general formula (2) in an amount of 5 mol % or more, further may contain 10 mol % or more, and further may contain 20 mol % or more.

[0054] From the viewpoint of improving light transmittance and surface hardness, it is preferable that at least one of the tetravalent group which is a tetracarboxylic acid residue of A and the divalent group which is a diamine residue of B contains an aromatic ring and at least one selected from the group consisting of (i) a fluorine atom, (ii) an aliphatic ring, and (iii) a structure in which aromatic rings are linked together by an alkylene group which may be substituted with a sulfonyl group or fluorine. The polyimide used in the present invention contains at least one selected from a tetracarboxylic acid residue having an aromatic ring and a diamine residue having an aromatic ring, and thus the molecular skeleton becomes rigid, the orientation is enhanced, and the surface hardness is improved. However, the rigid aromatic ring skeleton tends to extend the absorption wavelength to longer wavelengths, and the transmittance in the visible light region tends to decrease. On the other hand, when polyimide contains (i) fluorine atoms, the electronic state in the polyimide skeleton is made difficult to transfer charges, and thus the light transmittance is improved. When the polyimide contains (ii) an aliphatic ring, the conjugation of π electrons in the polyimide skeleton is broken, thereby inhibiting the movement of charges in the skeleton, and thus improving the light transmittance. When the polyimide contains (iii) a structure in which aromatic rings are linked together via a sulfonyl group or an alkylene group which may be substituted with fluorine, the conjugation of π electrons in the polyimide skeleton can be broken, thereby inhibiting the movement of charges in the skeleton, and thus improving the light transmittance. In particular, from the viewpoints of improving light transmittance and surface hardness, it is preferable that at least one of the tetravalent group which is the tetracarboxylic acid residue of A and the divalent group which is the diamine residue of B contains an aromatic ring and a fluorine atom, and it is preferable that the divalent group which is the diamine residue of B contains an aromatic ring and a fluorine atom.

[0055] The polyimide used in the present invention is such that the diamine residue having an aromatic ring or an aliphatic ring in B in the general formulas (1) and (2) is a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, a 3,3'-bis(trifluoromethyl)-4,4'-[(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)bis(4,1-phenyl)propane residue, From the viewpoints of light transmittance, bending resistance, and surface hardness, it is preferable that the divalent group contains at least one selected from the group consisting of a 2,2-bis[3-(3-aminophenoxy)phenyl]dianiline residue, a 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane residue, and a divalent group represented by the following general formula (3), and further contains at least one diamine residue of a diamine represented by the general formula (5). The polyimide used in the present invention is such that the diamine residue having an aromatic ring or an aliphatic ring in B in the general formulas (1) and (2) is a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, a 3,3'-bis(trifluoromethyl)-4,4'-[(1,1,1,3,3,3-hexafluoropropane-2 ,2-diyl)bis(4,1-phenyleneoxy)]dianiline residue, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane residue, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane residue, and at least one selected from the group consisting of a divalent group represented by the following general formula (3), and further including an N,N'-bis(4-aminophenyl)terephthalamide residue, a 4-aminophenyl-4-aminobenzo From the viewpoints of light transmittance, bending resistance, and surface hardness, it is preferable that the divalent group may contain at least one selected from the group consisting of a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, and a bis(4-aminophenyl)terephthalate residue: and may further comprise at least one selected from the group consisting of an N,N'-bis(4-aminophenyl)terephthalamide residue, a 4-aminophenyl-4-aminobenzoate residue, a (2-phenyl-4-aminophenyl)-4-aminobenzoate residue, and a bis(4-aminophenyl)terephthalate residue. The divalent group is preferably a divalent group which contains at least one selected from the group consisting of divalent groups represented by the following general formula (3) and further comprises N,More preferably, it is a divalent group which may contain at least one selected from the group consisting of N'-bis(4-aminophenyl)terephthalamide residue, 4-aminophenyl-4-aminobenzoate residue, (2-phenyl-4-aminophenyl)-4-aminobenzoate residue, and bis(4-aminophenyl)terephthalate residue. The divalent group represented by the following general formula (3) is R, 5 and R 6 More preferably, R is a perfluoroalkyl group, and among these, a perfluoroalkyl group having 1 to 3 carbon atoms is preferred, and a trifluoromethyl group or a perfluoroethyl group is more preferred. 5 and R 6 The alkyl group in is preferably an alkyl group having 1 to 3 carbon atoms, and more preferably a methyl group or an ethyl group.

[0056] [ka] (In the general formula (3), R 5 and R 6 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.

[0057] In the polyimide used in the present invention, from the viewpoints of light transmittance, bending resistance and surface hardness, in particular, the tetracarboxylic acid residue having an aromatic ring or an aliphatic ring in A in the general formula (2) is a cyclohexanetetracarboxylic acid dianhydride residue, a cyclopentanetetracarboxylic acid dianhydride residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid dianhydride residue, a cyclobutanetetracarboxylic acid dianhydride residue, a pyromellitic acid dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic acid dianhydride residue, a 2, It is preferably at least one tetravalent group selected from the group consisting of a 2',3,3'-biphenyltetracarboxylic dianhydride residue, a 2,3,3',4'-biphenyltetracarboxylic dianhydride residue, a 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 3,3'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 4,4'-oxydiphthalic anhydride residue, and a 3,4'-oxydiphthalic anhydride residue. In A in the general formula (2), the total amount of these suitable residues is preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.

[0058] In terms of improving surface hardness, A in the general formula (2) preferably contains at least one tetracarboxylic acid residue group (Group A) suitable for improving rigidity, such as at least one selected from the group consisting of pyromellitic dianhydride residue, 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, and 2,2',3,3'-biphenyltetracarboxylic dianhydride residue, and from the viewpoint of improving light transmittance, it is preferable that A contains at least one tetracarboxylic acid residue group (Group A) suitable for improving rigidity, such as at least one selected from the group consisting of cyclohexanetetracarboxylic dianhydride residue, cyclopentanetetracarboxylic dianhydride residue, dicyclohexane-3,4,3',4'-tetracarboxylic dianhydride residue, cyclobutanetetracarboxylic dianhydride residue, It is preferable that the tetracarboxylic acid dianhydride group contains at least one tetracarboxylic acid residue group (Group B) suitable for improving light transmittance, such as at least one selected from the group consisting of tetracarboxylic acid dianhydride residues, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride residues, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride residues, 4,4'-oxydiphthalic anhydride residues, and 3,4'-oxydiphthalic anhydride residues, and the Group B may be used in combination with Group A. When Group A and Group B are mixed, the content ratio of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) to the tetracarboxylic acid residue group suitable for improving the light transmittance (Group B) is preferably 0.05 mol or more and 9 mol or less, more preferably 0.1 mol or more and 5 mol or less, and even more preferably 0.3 mol or more and 4 mol or less, of the tetracarboxylic acid residue group suitable for improving the rigidity (Group A) per 1 mol of the tetracarboxylic acid residue group suitable for improving the light transmittance (Group B). Among these, it is preferable for Group B to contain at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, and cyclobutane tetracarboxylic dianhydride residues in terms of improving surface hardness and light transmittance, and it is more preferable for Group B to contain cyclobutane tetracarboxylic dianhydride residues in terms of a high effect of reducing yellowness and excellent elastic modulus.

[0059] The content ratio of each repeating unit in the polyimide, and the content ratio (mol%) of each tetracarboxylic acid residue and each diamine residue can be determined from the molecular weight of the charged material during the production of the polyimide. The content ratio (mol%) of each tetracarboxylic acid residue and each diamine residue in the polyimide can be determined by using high performance liquid chromatography, gas chromatography mass spectrometry, NMR, elemental analysis, XPS / ESCA, and TOF-SIMS for the decomposition product of the polyimide. The decomposition product of the polyimide can be obtained, for example, by decomposing the sample with an alkaline aqueous solution or supercritical methanol.

[0060] The polyimide used in the present invention is selected from those having a weight average molecular weight of 100,000 or more and 270,000 or less, calculated as polystyrene by gel permeation chromatography, because it is less likely to cause bubble defects and has good bending resistance. From the viewpoint of flex resistance, the weight average molecular weight may be 120,000 or more, further 140,000 or more, and further 160,000 or more. On the other hand, from the viewpoint of solubility, the weight average molecular weight may be 250,000 or less, further 230,000 or less, and further 210,000 or less. The weight-average molecular weight of polyimide can be measured by gel permeation chromatography (GPC). Specifically, polyimide is dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.1% by mass, and a 30 mmol% LiBr-NMP solution with a water content of 500 ppm or less is used as the developing solvent. Measurements are performed using a Tosoh GPC device (HLC-8120, column used: SHODEX GPC LF-804) with a sample injection volume of 50 μL, a solvent flow rate of 0.4 mL / min, and 37°C. The weight-average molecular weight is determined based on a polystyrene standard sample with the same concentration as the sample.

[0061] 2. Additives The polyimide film of the present invention may further contain additives, if necessary, in addition to the polyimide, such as inorganic particles, silica filler for facilitating winding, surfactants for improving film-forming properties and defoaming properties, and ultraviolet absorbers.

[0062] 3. Characteristics of polyimide film The polyimide film of the present invention preferably further has the properties described below. (1) Residual Solvent As described later, the polyimide film of the present invention is preferably produced using an organic solvent containing dichloromethane in an amount of 90 mass % or more based on the total amount of organic solvent, since this makes it easier to obtain a polyimide film that is less susceptible to bubble defects, has good film thickness uniformity, and has good bending resistance. Therefore, the polyimide film of the present invention preferably contains dichloromethane as a residual solvent in an amount of 1 ppm or more and 2000 ppm or less, in view of being less susceptible to bubble defects, having good film thickness uniformity, and having good bending resistance. In the polyimide film of the present invention, the dichloromethane content is preferably 1000 ppm or less, more preferably 800 ppm or less, even more preferably 400 ppm or less, and even more preferably 100 ppm or less, from the viewpoint of improving the static bending resistance and the dynamic bending resistance, and the dichloromethane content is preferably as small as possible, and may be about 1 ppm, which is the detection limit described later. In addition, in order to improve the bending resistance of the polyimide film of the present invention, the content of an organic solvent having a boiling point of 70°C or more, particularly 100°C or more, at 1 atmospheric pressure is preferably 1000 ppm or less, more preferably 800 ppm or less, even more preferably 400 ppm or less, and even more preferably 100 ppm or less.

[0063] The amount of residual solvent in the polyimide film can be measured as follows. [Identifying types of residual solvents] First, the type of residual solvent is identified using a GC-MS connected to a purge & trap device (thermal desorption device). A sample tube containing 10 mg of polyimide film was placed in a purge and trap device (product name JTD505-III, Japan Analytical Industry Co., Ltd.) and heated at 200°C for 30 minutes. The generated gas was collected in a trap tube at -60°C, and the collected material was heated to 315°C to remove the gas and send it to a GC-MS for qualitative analysis of the components of the generated organic gas. (Purge & trap device conditions) Total split ratio (intake volume / exhaust volume) 1:10, Carrier gas: Helium 1.0ml / min, constant (GC-MS conditions) Instrument name: GC-MS instrument (Agilent, 6890 / 5973 GC / MS) Column: UA-5, inner diameter 250 μm × length 30 m × film thickness 0.25 μm (manufactured by Frontier Labs), heating conditions: 50°C (hold for 5 minutes) → 10°C / min (heat) → 320°C (hold for 3 minutes)

[0064] [Quantitative analysis of residual solvents] A polyimide film is added to N,N-dimethylformamide (DMF) so that the concentration of the polyimide film is 5% by mass, and a polyimide film / N,N-dimethylformamide (DMF) solution is prepared. An internal standard solution (0.2% by mass anisole / DMF solution) is added to this solution to prepare a sample solution. The sample solution is subjected to GC-MS measurement under the following conditions using a GC-MS device (e.g., Agilent, 6890 / 5973 GC / MS). The GC-MS measurement is performed three times, and the measurement result is the average value of the three measurements. (GC conditions) Column: InertCapWax inner diameter 250 μm × length 30 m × film thickness 0.25 μm (GL Sciences), Sample injection volume: 0.2 uL; split ratio (inlet volume / exhaust volume): 1:50; carrier gas: helium 94.3 kPa constant pressure; injection port temperature: 250°C; heating conditions: 40°C (5 min hold) → 5°C / min → 120°C → 20°C / min → 240°C (6 min hold); transfer line temperature: 250°C (MS conditions) Ionization method: EI, measurement mode: SIM, ion source temperature: 250°C, quadrupole temperature: 150°C, ionization voltage: 70eV

[0065] A calibration curve is prepared for each of the residual solvents identified as above, and the amount of each residual solvent is quantified based on the calibration curve. For example, when the residual solvent contained is dichloromethane, GC-MS measurement is performed for each calibration curve solution prepared by adding an internal standard solution to each dichloromethane (target compound) / DMF solution prepared so that the dichloromethane content is, for example, 0.01 mass%, 0.05 mass%, or 0.1 mass%, in the same manner as the above-mentioned sample solution, to prepare the calibration curve. The GC-MS measurement is performed three times, and the measurement result is the average value of the three measurements. The content of dichloromethane is calculated as a mass ratio to the polyimide film based on the calibration curve. The calibration curve is appropriately reconstructed depending on the amount detected. When two or more types of residual solvents are contained, a calibration curve solution is prepared for each residual solvent as in the case of dichloromethane above, and the calibration curve created from the measurement results of GC-MS measurement for each calibration curve solution is used as the basis. If N,N-dimethylformamide (DMF) is contained as a residual solvent, prepare a sample solution using a good solvent for polyimide that does not contain DMF as a residual solvent, such as N-methyl-2-pyrrolidone.

[0066] (2) Total light transmittance From the viewpoint of transparency, the polyimide film of the present invention preferably has a total light transmittance measured in accordance with JIS K7361-1 of 85.0% or more, more preferably 88.0% or more, and even more preferably 89.0% or more.

[0067] The total light transmittance measured in accordance with JIS K7361-1 can be measured, for example, by a haze meter (e.g., HM150 manufactured by Murakami Color Research Laboratory). Note that the total light transmittance at a different thickness can be calculated from the measured value of the total light transmittance at a certain thickness according to the Beer-Lambert law, and this can be used. Specifically, according to the Beer-Lambert law, the transmittance T is Log 10 (1 / T)=kcb (k = material-specific constant, c = concentration, b = optical path length). In the case of film transmittance, if we assume that the density is constant even if the film thickness changes, c is also a constant, so the above formula can be written as follows using the constant f: Log 10 (1 / T)=fb (f=kc). Here, if the transmittance at a certain film thickness is known, the constant f specific to each material can be calculated. Therefore, T=1 / 10 f·b By using this formula, substituting a specific constant for f and the target film thickness for b, the transmittance for the desired film thickness can be calculated.

[0068] (3) Yellowness The polyimide film of the present invention preferably has a yellowness index (YI value) calculated in accordance with JIS K7373-2006 of 12.0 or less. A low yellowness index is preferable in that yellow coloring is suppressed and light transmittance is improved. The yellowness index (YI value) calculated in accordance with JIS K7373-2006 is more preferably 10.0 or less, even more preferably 7.0 or less, even more preferably 5.0 or less, and particularly preferably 4.5 or less. The yellowness index (YI value) can be calculated in accordance with JIS K7373-2006 by using an ultraviolet-visible-near-infrared spectrophotometer (e.g., V-7100 by JASCO Corporation) using auxiliary illuminant C and a 2-degree visual field, based on the transmittance measured at 1 nm intervals in the range of 250 nm to 800 nm, and determining tristimulus values ​​X, Y, and Z in the XYZ color system based on the transmittance. The YI value can then be calculated from the X, Y, and Z values ​​using the following formula. YI=100(1.2769X-1.0592Z) / Y In addition, from the measured value of yellowness at a certain thickness, the yellowness at a different thickness can be calculated and used by calculating the conversion value of each transmittance at each wavelength at different thicknesses using Lambert-Beer's law for each transmittance at each wavelength measured at 1 nm intervals between 250 nm and 800 nm of a sample of a certain film thickness, in the same manner as for the total light transmittance described above.

[0069] Furthermore, since the polyimide film of the present invention is suppressed from yellowing and has improved light transmittance, and can be suitably used as a glass replacement material, the value obtained by dividing the yellowness index (YI value) calculated in accordance with JIS K7373-2006 by the film thickness (μm) (YI value / film thickness (μm)) is preferably 0.10 or less, more preferably 0.04 or less, and even more preferably 0.03 or less. In the present invention, the value obtained by dividing the yellowness index (YI value) by the film thickness (μm) (YI value / film thickness (μm)) is rounded to two decimal places in accordance with Rule B of JIS Z8401:1999.

[0070] (4) Haze value The haze value of the polyimide film of the present invention may be 2.0 or less, more preferably 1.0 or less, and even more preferably 0.5 or less, from the viewpoint of light transmittance. The haze value can be preferably achieved when the polyimide film has a thickness of 5 μm or more and 100 μm or less. The haze value can be measured by a method in accordance with JIS K-7136, for example, by using a haze meter HM150 manufactured by Murakami Color Research Laboratory.

[0071] (5) Tensile modulus The polyimide film of the present invention preferably has a tensile modulus of 3.3 GPa or more at 25°C measured on a 10 mm x 150 mm test piece in accordance with JIS K7127 at a tensile speed of 50 mm / min and a chuck distance of 100 mm. Thus, when the tensile modulus at 25°C (room temperature) is high, the film can maintain a sufficient surface hardness as a protective film even at room temperature, and can be used as a surface material or a substrate. The tensile modulus is more preferably 4.0 GPa or more, even more preferably 4.5 GPa or more, and even more preferably 5.0 GPa or more. On the other hand, the tensile modulus may be 8.0 GPa or less from the viewpoint of improving bending resistance. The tensile modulus can be measured by cutting a test piece of width 10 mm × length 150 mm from a polyimide film using a tensile tester (e.g., Shimadzu Corporation: Autograph AG-X 1N, load cell: SBL-1KN) at 25° C., a pulling speed of 50 mm / min, and a chuck distance of 100 mm. The polyimide film used to determine the tensile modulus preferably has a thickness of 50 μm±5 μm.

[0072] (6) Composite elastic modulus The polyimide film of the present invention preferably has a composite elastic modulus of 5.3 GPa or more. When the composite elastic modulus is high, the film can maintain a sufficient surface hardness as a protective film even at room temperature, and can be used as a surface material or a substrate. The composite elastic modulus is more preferably 5.5 GPa or more, further preferably 5.7 GPa or more, and even more preferably 6.0 GPa or more. On the other hand, the composite elastic modulus may be 10 GPa or less from the viewpoint of improving the bending resistance.

[0073] Here, the composite elastic modulus is the indentation hardness (H IT ) is measured using the contact projection area A p The indentation hardness is calculated using the following formula: "Indentation hardness" is a value determined from the load-displacement curve from loading to unloading of the indenter obtained by hardness measurement using the nanoindentation method. The composite elastic modulus of a polyimide film is an elastic modulus that includes the elastic deformation of the polyimide film and the elastic deformation of the indenter.

[0074] Indentation hardness (H IT) is measured on the measurement sample using a "TI950 TriboIndenter" manufactured by BRUKER. Specifically, first, a block is prepared by embedding a polyimide film cut to 1 mm x 10 mm in embedding resin, and a uniform slice having a thickness of 50 nm to 100 nm without holes is cut from this block by a general slice preparation method. An "Ultramicrotome EM UC7" (manufactured by Leica Microsystems) or the like can be used to prepare the slice. The remaining block from which the uniform slice without holes is cut is used as the measurement sample. Next, in the cross section obtained by cutting out the slice in such a measurement sample, a Berkovich indenter (triangular pyramid, TI-0039 manufactured by BRUKER) is pressed vertically into the center of the cross section of the polyimide film for 10 seconds up to a maximum pressing load of 25 μN under the following measurement conditions. Here, in order to avoid the influence of the side edges of the polyimide film, the Berkovich indenter is pressed into the polyimide film at a distance of 500 nm from each of the two ends toward the center of the polyimide film. After that, the pressure is held constant to relax the residual stress, and the load is removed over 10 seconds to measure the maximum load after relaxation. max (μN) and contact projection area A p (nm 2 ) and P max / A p The indentation hardness (H IT The above contact projected area is the contact projected area corrected for the indenter tip curvature by the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER). Indentation hardness (H IT ) is the arithmetic average of values ​​obtained by measuring at 10 locations. If any of the measured values ​​deviate from the arithmetic average by more than ±20%, those measured values ​​shall be excluded and remeasured. Whether or not any of the measured values ​​deviate from the arithmetic average by more than ±20% shall be determined by whether the value (%) calculated by (AB) / B×100, where A is the measured value and B is the arithmetic average, is more than ±20%. (Measurement conditions) ·Loading speed: 2.5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 2.5μN / sec ·Measurement temperature: 25℃

[0075] Polyimide film composite elastic modulus E r is the contact projection area A obtained during the measurement of indentation hardness according to the following formula (1). p The composite elastic modulus is calculated by measuring the indentation hardness at 10 points, calculating the composite elastic modulus each time, and taking the arithmetic average of the composite elastic moduli obtained at the 10 points.

[0076]

number

[0077] (7)tanδ curve The polyimide film of the present invention preferably has a peak apex in a tan δ curve, which is a value obtained by dividing the loss modulus by the storage modulus, only in a temperature range of 150° C. or higher. If the peak apex in the tan δ curve is located below 150° C., the molecular chains of the polyimide are likely to move and are likely to undergo plastic deformation, which may result in poor flexural resistance. On the other hand, if the peak apex is not located below 150° C., the mobility of the molecular chains is suppressed, making it difficult to undergo plastic deformation, and the flexural resistance can be improved. Furthermore, when the tan δ curve has a peak only in a temperature region of 150°C or higher, the bending resistance is prevented from being impaired due to thermal deformation even in a high-temperature environment, such as inside a car in summer, and therefore the bending resistance is improved even in a high-temperature environment. Furthermore, if the tan δ curve has peaks only in a temperature range of 150° C. or higher, the tensile modulus tends to be high and the surface hardness tends to be high. From the viewpoint of improving bending resistance and surface hardness, the polyimide film of the present invention preferably has a peak apex in the tan δ curve only in a temperature range of 200° C. or higher, even more preferably only in a temperature range of 250° C. or higher, and even more preferably only in a temperature range of 300° C. or higher. On the other hand, from the viewpoint of reducing the bake temperature, the peak apex in the tan δ curve is preferably in a temperature range of 380° C. or lower. The tan δ curve is obtained from the relationship between temperature and tan δ (tan δ=loss modulus (E″) / storage modulus (E′)) by dynamic viscoelasticity measurement, and the temperature at the apex of the peak where the peak maximum value is the largest can be used as an index of the glass transition temperature. Dynamic viscoelasticity measurement can be performed, for example, with a dynamic viscoelasticity measuring device RSA-G2 (TA Instruments Japan Co., Ltd.) with a measurement range of −150° C. to 490° C., a frequency of 1 Hz, and a temperature rise rate of 5° C. / min. In addition, the measurement can be performed with a sample width of 5 mm and a chuck distance of 20 mm. When analyzing the peaks and inflection points, the data is quantified and analyzed from the numerical values ​​without visual evaluation. In a curve of temperature (horizontal axis) and tan δ (tan δ=loss modulus (E″) / storage modulus (E')) (vertical axis), a peak refers to a maximum value of tan δ of 0.2 or more, preferably 0.3 or more, and a peak width between the valleys of the peak of 3°C or more. Small upward and downward fluctuations in the curve resulting from measurement noise, etc. are not observed as the peak at the apex of the peak. The sample for measuring the tan δ curve is a polyimide film that has been left to stand for 24 hours in an environment of 23°C ± 2°C and RH 30-50%, and then a sample of 10 cm square or more is taken. The central part of the film is cut into a piece 5 mm wide x 50 mm long (so that the sample length is 20 mm when chucked) using a cutting tool with a 5 mm wide slit made with a razor or scalpel. The width is measured using a caliper, and the average value of three measurements taken at different positions is recorded. If any part of the width measurement varies by 3% or more from the average value, do not use that sample.

[0078] (8)Pencil hardness The polyimide film of the present invention preferably has a pencil hardness of 2B or more, more preferably B or more, and even more preferably HB or more. The pencil hardness of the polyimide film can be measured by subjecting a measurement sample to humidity conditioning for 2 hours under conditions of a temperature of 25° C. and a relative humidity of 60%, and then subjecting the film surface to a pencil hardness test (load of 0.98 N) as specified in JIS K5600-5-4 (1999) using a test pencil as specified in JIS-S-6006, and evaluating the highest pencil hardness that does not cause scratches. For example, a pencil scratch coating hardness tester manufactured by Toyo Seiki Co., Ltd. can be used.

[0079] 4.Polyimide film composition The thickness of the polyimide film of the present invention may be appropriately selected depending on the application, but may be 1 μm or more, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and may be 35 μm or more. On the other hand, it is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and even more preferably 90 μm or less. If the thickness is too thin, the strength decreases, whereas if the thickness is too thick, the difference between the inner diameter and the outer diameter when bent increases, which increases the load on the film and may decrease the bending resistance.

[0080] The polyimide film of the present invention may be subjected to a surface treatment such as saponification treatment, glow discharge treatment, corona discharge treatment, ultraviolet treatment, or flame treatment.

[0081] 5. Polyimide film manufacturing method The method for producing the polyimide film of the present invention is not particularly limited as long as it can produce the polyimide film of the present invention. For example, the polyimide film may be produced by the first production method or the second production method described below.

[0082] 5-1. First manufacturing method When the polyimide has good solubility in an organic solvent, it is preferable to use the first polyimide production method, in which the polyimide is dissolved in an organic solvent, and then dried using a polyimide varnish containing an additive as necessary, to produce a polyimide film. The polyimide used in the present invention has a tetracarboxylic acid residue having a specific structure including a parabiphenylene group with a twisted dihedral angle via an ester bond in the main chain, and is therefore easily soluble in an organic solvent. When the polyimide has a solvent solubility such that it dissolves in an organic solvent at 25° C. in an amount of 6% by mass or more, the first production method can be suitably used.

[0083] The first method for producing a polyimide film includes the steps of: A step of preparing a polyimide varnish containing the polyimide used in the present invention and an organic solvent, the polyimide content in the polyimide varnish being 6% by mass or more and 15% by mass or less, and having a viscosity of 1,000 to 10,000 cps at 25°C as measured by a rotational viscometer; applying the polyimide varnish to a substrate, drying the polyimide varnish at a temperature of 100° C. or less, and peeling the coating film from the substrate after drying; It is preferable to have a process of fixing the ends of the dried coating film peeled off from the support and then heating the dried coating film at a temperature of 150°C or higher, since this makes it difficult for air bubble defects to occur and makes it easy to reduce the amount of residual solvent. In particular, by drying the organic solvent at two or more drying temperatures below 100°C, it is possible to suppress the formation of skin on the coating surface and the formation of bubbles due to bumping of the organic solvent in the coating. Skinning refers to a state in which the coating surface is more dried than the interior, a concentration gradient occurs in the coating thickness direction, and the solvent diffusion is hindered in the outermost skin layer, making the drying rate-limiting. Skinning can cause the evaporated solvent in the coating to expand, generating bubble defects. Heating the peeled, dried coating film to 150°C or higher is also preferably done at two or more heating stages at temperatures of 150°C or higher, as this makes it difficult for bubble defects to occur and makes it easier to reduce the amount of residual solvent. For example, when the thickness of the coating film after drying is less than 50 μm, it is preferable that the holding time at each stage be 10 minutes or more and less than 60 minutes, and when the thickness of the coating film after drying is 50 μm or more and 100 μm or less, it is preferable that the holding time at each stage be 30 minutes or more and less than 90 minutes. Examples of the organic solvent used in the polyimide varnish include aprotic polar solvents and water-soluble alcohol solvents, and specific examples thereof include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, and dichloromethane.

[0084] Among the first production methods, the production by the production method of the polyimide film of the present invention described later is preferable. The method for producing a polyimide film of the present invention comprises the steps of: A polyimide varnish containing a polyimide and an organic solvent, The polyimide contains 10 mol % or more and 100 mol % or less of the constitutional unit represented by the general formula (1) and (100-x) mol % (wherein x is the mol % of the constitutional unit represented by the general formula (1)) of the constitutional unit represented by the general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less as calculated on a polystyrene basis by gel permeation chromatography; The organic solvent contains dichloromethane in an amount of 90% by mass or more based on the total amount of the organic solvent. A step of preparing a polyimide varnish having a content ratio of the polyimide in the polyimide varnish of 6% by mass or more and 15% by mass or less, and a viscosity at 25°C measured by a rotational viscometer of 1,000 to 10,000 cps; applying the polyimide varnish to a substrate, drying the polyimide varnish at a temperature of 40° C. or less, and peeling the coating film from the substrate after drying; The method includes a step of fixing the end portion of the dried coating film peeled from the support, and then heating the dried coating film at a temperature of 150° C. or higher.

[0085] According to the method for producing a polyimide film of the present invention, the polyimide content in the varnish can be increased to a sufficient concentration, and the viscosity of the varnish can be adjusted to a desired range, so that even polyimide films with a thickness of 30 μm or more can be easily produced, and films with good thickness uniformity can be obtained without causing bubble defects. Since an organic solvent containing 90 mass % or more of dichloromethane with a boiling point of 40° C. in the total organic solvent is used, there is no need to heat at a high temperature or perform forced drying with hot air during drying, and foaming, uneven thickness, yellowing, etc. of the film can be suppressed, the amount of residual solvent can be reduced, and bending resistance can be improved. The following will mainly describe in detail the method for producing a polyimide of the present invention, which is preferable among the first production method, but the following description can be applied to the first production method in general, except for the organic solvent and drying temperature.

[0086] (1) Preparation of polyimide varnish The polyimide varnish of the present invention is a polyimide varnish containing a polyimide and an organic solvent, The polyimide contains 10 mol % or more and 100 mol % or less of the constitutional unit represented by the general formula (1) and (100-x) mol % (wherein x is the mol % of the constitutional unit represented by the general formula (1)) of the constitutional unit represented by the general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less as calculated on a polystyrene basis by gel permeation chromatography; The organic solvent contains dichloromethane in an amount of 90% by mass or more based on the total amount of the organic solvent. The content of the polyimide in the polyimide varnish is 6% by mass or more and 15% by mass or less. When the polyimide varnish of the present invention is used in the method for producing a polyimide film of the present invention, it is adjusted so that the viscosity at 25° C. measured with a rotational viscometer is 1,000 to 10,000 cps.

[0087] (1-1) Polyimide The polyimide containing 10 mol % or more and 100 mol % or less of the structural unit represented by the general formula (1) and (100-x) mol % (wherein x is the mol % of the structural unit represented by the general formula (1)) of the structural unit represented by the general formula (2) and having a weight average molecular weight of 100,000 or more and 270,000 or less as calculated in terms of polystyrene by gel permeation chromatography may be the same as the polyimide described in the polyimide film of the present invention, and therefore further description thereof will be omitted here. The method for producing the polyimide is not particularly limited. For example, the polyimide can be produced by reacting one or more tetracarboxylic dianhydrides, including a tetracarboxylic dianhydride represented by the following general formula (4) and, if necessary, a tetracarboxylic dianhydride having an aromatic ring or an aliphatic ring, with a diamine having one or more aromatic rings or aliphatic rings, through a process of obtaining a polyimide precursor (polyamic acid) containing 10 mol % or more and 100 mol % or less of a structural unit represented by the following general formula (1') and (100-x) mol % (where x is the mol % of the structural unit represented by the general formula (1')) of a structural unit represented by the following general formula (2'), and a process of imidizing the obtained polyimide precursor (polyamic acid).

[0088] [ka] (In the general formula (4), R 1 ~R 4 is the same as in the general formula (1).

[0089] [ka] (In the general formulas (1') and (2'), R 1 ~R 4 , A, and B are the same as those in the general formulas (1) and (2), respectively.

[0090] The tetracarboxylic dianhydride represented by the general formula (4) can be obtained by a known esterification reaction using the corresponding biphenyl 4,4'-diol and trimellitic acid. The trimellitic acid includes trimellitic anhydride and trimellitic anhydride halide. The tetracarboxylic acid dianhydride having an aromatic ring or an aliphatic ring and the diamine having one or more aromatic rings or aliphatic rings, which are used as necessary, may be the same as those described for the polyimide film.

[0091] The polyimide precursor is obtained by reacting the above-mentioned tetracarboxylic dianhydride with the above-mentioned diamine in a solvent. The solvent used for synthesizing the polyimide precursor (polyamic acid) is not particularly limited as long as it can dissolve the above-mentioned tetracarboxylic dianhydride and diamine, and for example, an aprotic polar solvent or a water-soluble alcohol solvent can be used. In the present invention, it is preferable to use an organic solvent containing a nitrogen atom such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, or γ-butyrolactone. The organic solvent is a solvent containing a carbon atom.

[0092] The polymerization reaction procedure can be appropriately selected from known methods. For example, in a reaction vessel, first, a diamine is dissolved in a polymerization solvent, and to this solution, an acid dianhydride in an amount substantially equimolar to the diamine is gradually added, followed by stirring using a mechanical stirrer or the like at a temperature in the range of 0 to 100° C., preferably 20 to 60° C., for 0.5 to 150 hours, preferably 1 to 48 hours. In this case, the monomer concentration is usually in the range of 5 to 50% by mass, preferably 10 to 40% by mass.

[0093] In addition, when the polyimide precursor solution is prepared by combining at least two kinds of acid dianhydrides, the acid dianhydride may be added to a polymerization solvent in which a diamine is dissolved to synthesize a polyamic acid, or at least two kinds of acid dianhydrides may be added in a stepwise manner in an appropriate molar ratio to a reaction solution to control to some extent the sequence in which each raw material is incorporated into a polymer chain. For example, a tetracarboxylic dianhydride represented by general formula (4) may be added to a reaction solution in which a diamine has been dissolved, and reacted to synthesize an amic acid in which the tetracarboxylic dianhydride represented by general formula (4) reacts with a diamine, and then a tetracarboxylic dianhydride different from the tetracarboxylic dianhydride represented by general formula (4) may be added thereto, and further diamine may be added as necessary to polymerize a polyamic acid. When polymerized by this method, the tetracarboxylic dianhydride represented by general formula (4) is introduced into the polyamic acid in a linked form via one diamine. Polymerizing polyamic acid by such a method is preferable because it allows the positional relationship of tetracarboxylic acid residues having a specific structure, which contains a para-biphenylene group with a twisted dihedral angle via an ester bond in the main chain, to be specified to a certain extent, and makes it easy to obtain a polyimide film having good surface hardness and excellent bending resistance.

[0094] When the number of moles of diamine in the polyimide precursor solution (polyamic acid solution) is a and the number of moles of tetracarboxylic dianhydride is b, b / a is preferably 0.9 to 1.1, more preferably 0.95 to 1.05, even more preferably 0.97 to 1.03, and particularly preferably 0.99 to 1.01. By setting it in such a range, the molecular weight (degree of polymerization) of the obtained polyamic acid can be appropriately adjusted.

[0095] In order to prepare a polyimide having a weight average molecular weight of 100,000 or more and 270,000 or less as calculated using polystyrene standards by gel permeation chromatography, it is preferable to carry out the reaction by gradually adding an acid dianhydride to a reaction solution in which a diamine is dissolved, while measuring by gel permeation chromatography that the molecular weight reaches a desired range, in the preparation of the polyimide precursor.

[0096] From the viewpoint of improving bending resistance, the polyimide precursor (polyamic acid) has a weight average molecular weight of preferably 50,000 or more, more preferably 80,000 or more, and even more preferably 100,000 or more. On the other hand, from the viewpoint of suppressing bubble defects, the polyimide precursor (polyamic acid) has a weight average molecular weight of preferably 350,000 or less, more preferably 300,000 or less, and even more preferably 270,000 or less. The weight average molecular weight of the polyimide precursor can be measured by gel permeation chromatography (GPC). The polyimide precursor is dissolved in N-methylpyrrolidone (NMP) at a concentration of 0.5% by mass, and the developing solvent is a 10 mmol% LiBr-NMP solution with a water content of 500 ppm or less. Measurements are performed using a Tosoh GPC device (HLC-8120, column used: SHODEX GPC LF-804) with a sample injection volume of 50 μL, a solvent flow rate of 0.5 mL / min, and 40° C. The weight average molecular weight is determined based on a polystyrene standard sample of the same concentration as the sample.

[0097] As the polyimide precursor (polyamic acid) used for imidization, a polyimide precursor solution obtained by a synthesis reaction may be used as it is, or the solvent of the polyimide precursor solution may be dried and the solution may be dissolved in another solvent.

[0098] Methods for imidizing a polyimide precursor include thermal imidization, which involves a dehydration ring-closing reaction by heating, and chemical imidization, which involves a dehydration ring-closing reaction using a chemical imidization agent (a dehydration ring-closing agent).Of these, chemical imidization is preferred from the viewpoint of suppressing yellowing due to heating. When chemical imidization is performed, known compounds such as amines such as pyridine and β-picolinic acid, carbodiimides such as dicyclohexylcarbodiimide, and acid anhydrides such as acetic anhydride may be used as chemical imidization agents. The acid anhydride is not limited to acetic anhydride, but may include, but is not limited to, propionic anhydride, n-butyric anhydride, benzoic anhydride, trifluoroacetic anhydride, and the like. In addition, tertiary amines such as pyridine and β-picolinic acid may be used in combination. However, since these amines reduce the optical properties, especially the yellowness index (YI value), if they remain in the film, it is preferable to purify the reaction solution in which the polyimide precursor is reacted to polyimide by reprecipitation or the like, and remove the chemical imidization agent components other than polyimide to 100 ppm or less of the total weight of the polyimide.

[0099] The organic solvent used in the reaction solution for chemically imidizing the polyimide precursor is not particularly limited as long as it can dissolve the polyimide precursor. For example, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, and other nitrogen-containing organic solvents; γ-butyrolactone, etc. can be used.

[0100] A typical method for reprecipitating the reaction solution that has been reacted to form a polyimide is to drop the reaction solution into a large amount of poor solvent while stirring it. In terms of making it easier to reduce impurities, a preferred method for reprecipitating the reaction solution is to dilute the reaction solution that has been reacted to form a polyimide to an appropriate concentration as necessary, and then gradually add a poor solvent for the polyimide to the reaction solution to precipitate the polyimide. When the poor solvent is dropped to precipitate a polyimide, the solids concentration of the reaction liquid (polyimide solution) is preferably 0.1% by mass or more and 30% by mass or less, and more preferably 1% by mass or more and 10% by mass or less, from the viewpoints of yield and efficient removal of impurities. In order to adjust the solids concentration of the polyimide solution to a level suitable for precipitation of the polyimide, the polyimide solution may be appropriately diluted with a good solvent for the polyimide. As a guideline, a good solvent for polyimide can be appropriately selected from solvents in which the solubility of polyimide at 25° C. is 20 g / 100 g or more. Moreover, the poor solvent for polyimide can be appropriately selected from solvents in which the solubility of polyimide at 25° C. is less than 20 g / 100 g, as a guideline.

[0101] For example, an organic solvent that is a good solvent for polyimide, such as n-butyl acetate, is added to the reaction solution that has been reacted to form a polyimide, and the reaction solution is diluted by stirring until it becomes uniform, and then an alcohol-based organic solvent, such as t-butanol, methanol, ethanol, isopropyl alcohol, 2-butanol, cyclohexanol, or t-amyl alcohol, is gradually added to precipitate the polyimide, to obtain a white slurry, which is then filtered to obtain the polyimide. As the alcohol-based organic solvent, it is preferable to use a secondary or tertiary alcohol, and it is more preferable to use a tertiary alcohol, in view of the excellent stability of the polyimide.

[0102] The polyimide obtained by reprecipitation as described above is preferably washed repeatedly with an organic solvent to remove residual solvent. By reducing the residual solvent in the polyimide material with a boiling point of 70°C or higher, especially 100°C or higher, at 1 atmospheric pressure to 100 ppm or lower, the bending resistance is further improved. For example, the polyimide obtained by reprecipitation is washed in an organic solvent for washing, and then filtered. This washing process is repeated, and the polyimide is dried at 100° C. to 120° C. using a vacuum dryer to obtain the polyimide. The organic solvent for washing is selected from among organic solvents that are highly compatible with the residual solvent contained in the polyimide obtained by reprecipitation, are poor solvents for the polyimide, and have a boiling point lower than the drying temperature of a vacuum dryer so that they can be completely volatilized by drying at 100°C to 120°C using a vacuum dryer. For example, when the residual solvent is N,N-dimethylacetamide, N-methyl-2-pyrrolidone, etc., used in preparing the polyimide precursor, isopropyl alcohol, methanol, etc. are preferably used as the cleaning organic solvent. One or more types of cleaning organic solvents can be used.

[0103] The content of the polyimide in the polyimide varnish is adjusted to 6% by mass or more and 15% by mass or less. By adjusting the concentration in this manner, air bubble defects are unlikely to occur even if the film has a thickness of 30 μm or more. The content of the polyimide may be appropriately selected from within this range so that the viscosity described below becomes appropriate.

[0104] (1-2) Organic solvents in varnish The organic solvent contained in the polyimide varnish of the present invention is an organic solvent containing dichloromethane in an amount of 90 mass % or more of the total organic solvent. The organic solvent other than dichloromethane, which may be contained in an amount of 10 mass % or less in the total organic solvents, can be appropriately selected according to the application from within a range that does not impair the solvent solubility of the polyimide. Examples of organic solvents different from dichloromethane that may be contained in an amount of 10 mass% or less in the total organic solvents include ethylene glycol monoethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-butyl ether, ethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ortho-dichlorobenzene, xylene, cresol, chlorobenzene, i-butyl acetate, i-pentyl acetate, n-butyl acetate, n-propyl acetate, n-pentyl acetate, cyclohexanol, cyclohexanone, 1,4-dioxane, tetrachloroethylene, toluene, methyl isobutyl ketone, methylcyclohexanol, methylcyclohexanone, methyl-n-butyl ketone, dichloroethane, methanol, ethanol, n-propanol, i-propanol, n-butanol, s-butanol, t-butanol, and mixed solvents thereof. For example, from the viewpoint of reducing the residual solvent in the film, it is preferable to use at least one of methanol and ethanol, and from the viewpoint of the solubility of polyimide, it is preferable to use at least one of dichloroethane and cyclohexanone.

[0105] The organic solvent contained in the polyimide varnish of the present invention preferably contains an organic solvent other than dichloromethane in an amount of 1 mass % or more, and more preferably 2 mass % or more, of the total organic solvent, in order to exhibit the function of the added organic solvent other than dichloromethane. Therefore, in terms of exerting the function of the added organic solvent different from dichloromethane, the dichloromethane content in the total organic solvents may be 99 mass % or less, or 98 mass % or less. From the viewpoint of reducing residual solvents, the dichloromethane content in the total organic solvents is preferably 95% by mass or more, and more preferably 97% by mass or more.

[0106] (1-3) Additives The varnish may contain additives as required. The additives may be the same as the additives that may be contained as required in the description of the polyimide film.

[0107] (1-4) Viscosity of varnish The polyimide varnish used in the method for producing a polyimide film of the present invention is selected so that the polyimide content in the polyimide varnish is in the range of 6% by mass to 15% by mass, and the viscosity at 25°C measured with a rotational viscometer is 1,000 to 10,000 cps. When the polyimide film is produced, if the viscosity of the polyimide varnish is less than 1,000 cps, the thickness uniformity of the polyimide film may deteriorate. On the other hand, if the viscosity of the polyimide varnish exceeds 10,000 cps during the production of the polyimide film, air bubble defects may easily occur in the polyimide film. The viscosity of the polyimide varnish can be measured at 25° C. using a single cylinder type rotational viscometer (for example, TVB-10 type viscometer manufactured by Toki Sangyo Co., Ltd.) according to the method described in JIS K7117-1.

[0108] (2) Pre-drying process Next, the method includes a step of applying the polyimide varnish to a support, drying the polyimide varnish at a temperature of 40° C. or less, and peeling the coating film from the support after drying. (2-1) A step of applying the polyimide varnish to a support In the step of applying the polyimide varnish to the support, the support to be used is not particularly limited as long as it has a smooth surface and is heat-resistant and solvent-resistant. For example, inorganic materials such as glass plates, metal plates with mirror-finished surfaces, etc. are included. The shape of the support is selected according to the application method, and may be, for example, a plate, a drum, a belt, or a sheet that can be wound around a roll.

[0109] The coating means is not particularly limited as long as it is a method capable of coating at a desired thickness, and for example, known means such as a die coater, comma coater, roll coater, gravure coater, curtain coater, spray coater, and lip coater can be used. The coating may be performed by a sheet-type coating apparatus or a roll-to-roll type coating apparatus. The step of applying the polyimide varnish to the support may be carried out in a closed space in order to reduce air bubble defects, and may be followed by a preliminary drying step.

[0110] (2-2) Pre-drying process After the polyimide varnish is applied to the support, it is dried at a temperature of 40° C. or less to evaporate the organic solvent in the varnish to 15 mass % or less, thereby forming a dried coating film. If the initial drying temperature exceeds 40°C when evaporating the organic solvent in the varnish, the coating film is likely to foam and air bubble defects are likely to occur. In addition, blowing heated air during the initial drying process tends to deteriorate the uniformity of the coating thickness. In contrast, in the present invention, the organic solvent in the varnish is an organic solvent containing 90% by mass or more of dichloromethane having a boiling point of 40°C, so that the dichloromethane in the varnish can be evaporated at a temperature of 40°C or less without blowing hot air or heating to a temperature above 40°C, making it difficult for air bubble defects to occur in the film, and improving the film thickness uniformity and appearance of the film surface.

[0111] Drying at a temperature of 40°C or less is preferably carried out at 30°C or less, and more preferably at a temperature of 15°C to 25°C. Among them, it is preferable from the viewpoint of reducing bubble defects to leave the polyimide varnish applied to the support in a sealed space, and evaporate dichloromethane while creating a dichloromethane atmosphere in the sealed space. The sealed space can be controlled so that the dichloromethane in the space is saturated vapor pressure, and examples of the sealed space include a method using a glove bag, a method using a glove box, and a method for industrial production in which the atmosphere immediately after coating is controlled so that the dichloromethane vapor pressure is 50% to 100% of the saturated vapor pressure using a continuous drying furnace, gradually reducing the dichloromethane vapor concentration, and finally removing it from the furnace. In the final stage of the pre-drying process in which the organic solvent in the varnish is evaporated, in order to improve the mechanical strength of the film, the dichloromethane atmosphere in the sealed space may be replaced with an inert gas atmosphere or an air atmosphere to evaporate the organic solvent.

[0112] The pre-drying time may be appropriately adjusted depending on the thickness of the polyimide varnish coating, the type of organic solvent other than dichloromethane, the drying temperature, etc., but is usually 5 to 60 minutes, preferably 10 to 40 minutes.

[0113] (2-3) Peeling off the paint film after drying Next, the dried coating film is peeled off from the support. By peeling the dried coating film from the support before carrying out the main drying at high temperatures described below, the organic solvent can be evaporated from both surfaces of the film in the main drying described below, making it possible to sufficiently reduce the residual solvent.

[0114] (3) Main drying process Next, the method includes a step of fixing the edge of the dried coating film peeled off from the support, and then heating the dried coating film at a temperature of 150° C. or higher. In the step of heating at a temperature of 150° C. or higher, it is preferable to remove as much residual solvent in the film as possible.

[0115] The dried coating film peeled off from the support is heated at a temperature of 150° C. or higher to prevent shrinkage during heating and to improve the appearance and film thickness uniformity, and the ends of the dried coating film are fixed before heating. If the ends of the dried coating film are not fixed, waviness is likely to occur in the polyimide film. As a method for fixing the ends of the dried coating film peeled off from the support, for example, when the dried coating film is in the form of a single sheet, the dried coating film is sandwiched between two metal frames having roughly the same outer dimensions as the dried coating film and appropriate inner dimensions, and the two metal frames and the dried coating film are fixed with a fixing jig. In addition, for example, when the dried coating film is in a roll shape, a method can be mentioned in which the ends of the dried coating film are fixed using an apparatus capable of conveying a film by holding both left and right ends of a continuous film with fixing jigs such as clips.

[0116] The drying means for the dried coating film peeled off from the support is not particularly limited as long as it is possible to dry the organic solvent in a heating process at a temperature of 150° C. or higher, and for example, an oven, a drying furnace, a hot plate, infrared heating, etc. can be used. When precise control of optical properties is required, the solvent is preferably dried in an inert gas atmosphere. The inert gas atmosphere is preferably a nitrogen atmosphere, and the oxygen concentration is preferably 100 ppm or less, more preferably 50 ppm or less. If the heat treatment is performed in air, the film may be oxidized, resulting in coloration and a decrease in performance.

[0117] The dried coating film peeled off from the support may be heated to a maximum temperature of 150° C. or higher. The heating temperature does not need to be as high as the heating temperature for imidization, and may be appropriately adjusted depending on the type and amount of organic solvent and residual solvent in the varnish and the thickness of the coating film. Under normal pressure, the maximum temperature is preferably in the range of 250°C or less, and more preferably in the range of 220°C or less. Under reduced pressure, the maximum temperature is preferably in the range of 200°C or less, and more preferably in the range of 180°C or less. The dried coating film peeled off from the support is preferably heated stepwise from room temperature to the maximum temperature. The heating rate is, for example, within the range of 3 to 50°C / min, and preferably within the range of 5 to 20°C / min. Examples of the stepwise heating include heating at 140°C for 1 to 3 minutes, heating at 170°C for 1 to 3 minutes, and heating at 200°C for 5 to 20 minutes. Even in the main drying process in which heating is performed at a maximum temperature of 150° C. or higher, the stepwise drying temperature and drying time can be appropriately adjusted depending on the type and amount of organic solvent and residual solvent in the varnish and the film thickness of the coating.

[0118] (4) Stretching process Furthermore, after the step of heating the dried coating film peeled off from the support at a temperature of 150° C. or higher, a stretching step of stretching the resulting polyimide resin coating film may be included.

[0119] In the stretching step, the stretching step of stretching from 101% to 10,000% is preferably performed while heating at 80° C. or higher, assuming that the initial dimension before stretching is 100%. The heating temperature during stretching is preferably within the range of the glass transition temperature of the polyimide ±50°C, and more preferably within the range of the glass transition temperature ±40°C. If the stretching temperature is too low, the film may not deform and sufficient orientation may not be induced. On the other hand, if the stretching temperature is too high, the orientation obtained by stretching may be relaxed by the temperature, and sufficient orientation may not be obtained.

[0120] The stretching ratio of the polyimide film is preferably 101% or more and 10000% or less, and more preferably 101% or more and 500% or less. By performing stretching within the above range, the surface hardness of the obtained polyimide film can be further improved.

[0121] The method of fixing the polyimide film during stretching is not particularly limited and is selected according to the type of stretching device, etc. The stretching method is also not particularly limited and, for example, a stretching device having a conveying device such as a tenter can be used to stretch the film while passing through a heating furnace. The polyimide film may be stretched in only one direction (longitudinal or transverse stretching), or may be stretched in two directions by simultaneous biaxial stretching, successive biaxial stretching, oblique stretching, etc.

[0122] 5-2. Second manufacturing method The polyimide film of the present invention may be produced by the second production method described below. That is, the polyimide film of the present invention can be produced by a process comprising the steps of: preparing a polyimide precursor resin composition containing a polyamic acid, which is a polyimide precursor, and an organic solvent; applying the polyimide precursor resin composition to a support to form a polyimide precursor resin coating film; The polyimide film may be produced by a method for producing a polyimide film, the method including a step of imidizing the polyimide precursor by heating. The second production method may further include a step of stretching at least one of the polyimide precursor resin coating film and a post-imidization coating film obtained by imidizing the polyimide precursor resin coating film.

[0123] (1) Polyimide precursor resin composition preparation step The polyimide precursor resin composition prepared in the second manufacturing method contains a polyimide precursor and an organic solvent, and may contain additives, etc., as necessary. As the polyimide precursor, the same polyimide precursor (polyamic acid) as described in the first manufacturing method can be used, so the description here is omitted. In addition, as the additive, the same additive as described in the polyimide film can be used.

[0124] The organic solvent used in the polyimide precursor resin composition is not particularly limited as long as it can dissolve the polyimide precursor. For example, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphoramide, 1,3-dimethyl-2-imidazolidinone, and other nitrogen atom-containing organic solvents; γ-butyrolactone, etc. can be used, and among them, it is preferable to use the nitrogen atom-containing organic solvent for the above-mentioned reasons.

[0125] The content of the polyimide precursor in the polyimide precursor resin composition is preferably 50% by mass or more, and more preferably 60% by mass or more, of the solid content of the resin composition in order to form a uniform coating film and a polyimide film having strength sufficient for handling, and the upper limit may be appropriately adjusted depending on the components contained. In order to form a uniform coating film and polyimide film, the organic solvent in the polyimide precursor resin composition is preferably 40% by mass or more, more preferably 50% by mass or more, and is preferably 99% by mass or less in the resin composition.

[0126] The viscosity of the polyimide precursor resin composition at 25° C. with a solid content of 15% by mass is preferably 1,000 cps or more and 10,000 cps or less in terms of forming a uniform coating film and polyimide film. The viscosity of the polyimide precursor resin composition can be measured using a viscometer (for example, TVE-22HT, Toki Sangyo Co., Ltd.) at 25° C. with a sample amount of 0.8 ml.

[0127] (2) Polyimide precursor resin coating film formation process In the step of applying the polyimide precursor resin composition to a support to form a polyimide precursor resin coating film, the support and application method used can be the same as those described in the first production method.

[0128] After the polyimide precursor resin composition is applied to the support, the solvent in the coating film is dried at a temperature of 150° C. or less, preferably from 30° C. to 120° C., until the coating film becomes tack-free. By setting the solvent drying temperature to 150° C. or less, imidization of polyamic acid can be suppressed. The drying time may be appropriately adjusted depending on the thickness of the polyimide precursor resin coating film, the type of solvent, the drying temperature, etc., but is usually 1 to 60 minutes, preferably 2 to 30 minutes. The method for drying the solvent is not particularly limited as long as it is possible to dry the solvent at the above temperature, and for example, the same method as that explained in the first production method can be used. When precise control of optical properties is required, the solvent is preferably dried in an inert gas atmosphere. The inert gas atmosphere is preferably a nitrogen atmosphere, and the oxygen concentration is preferably 100 ppm or less, more preferably 50 ppm or less. If the heat treatment is performed in air, the film may be oxidized, resulting in coloration and a decrease in performance.

[0129] (3) Imidization process In the second production method, the polyimide precursor is imidized by heating. In the present invention, in order to reduce the amount of residual solvent in the polyimide film, it is preferable to carry out a step of heating the polyimide precursor by peeling the polyimide precursor resin coating film from the support used for coating, and then heating the polyimide precursor. In order to prevent shrinkage during heating, it is preferable to heat the polyimide precursor after fixing the ends of the polyimide precursor resin coating film after peeling from the support. The ends of the polyimide precursor resin coating film can be fixed in the same manner as in the case of the coating film after drying in the above-mentioned first production method.

[0130] The imidization temperature may be appropriately selected depending on the structure of the polyimide precursor. In general, the temperature rise start temperature is preferably 30° C. or higher, and more preferably 100° C. or higher. Meanwhile, the temperature rise end temperature is preferably 250° C. or higher, and more preferably 270° C. or higher. Meanwhile, from the viewpoints of suppressing the appearance defect and strength reduction of the film and improving the light transmittance, the temperature rise end temperature is preferably 400° C. or lower, and more preferably 350° C. or lower. The atmosphere during the temperature increase for imidization is preferably an inert gas atmosphere.

[0131] The heating means for imidization is not particularly limited as long as it is possible to raise the temperature to the above-mentioned temperature, and the same heating means as in the first production method described above can be used.

[0132] In the second manufacturing method, when the stretching step is included, it is preferable to set the imidization rate of the polyimide precursor to 50% or more before the stretching step, in order to suppress the appearance defect and whitening of the film. In particular, it is preferable to set the imidization rate to 80% or more in the imidization step before the stretching step, in order to improve the surface hardness of the polyimide film, and it is preferable to proceed with the reaction to 90% or more, and even 100%. It is presumed that the surface hardness is improved by stretching after imidization, since the rigid polymer chains are easily oriented. The imidization rate can be measured by infrared (IR) spectrum analysis or the like.

[0133] To obtain a final polyimide film, it is preferable to allow the reaction to proceed to an imidization degree of 90% or more, more preferably 95% or more, and even up to 100%. In order to progress the reaction to imidization to 90% or more, and even 100%, it is preferable to hold the temperature at the end of the temperature rise for a certain period of time, and the holding time is usually 1 to 180 minutes, and more preferably 5 to 150 minutes.

[0134] (4) Stretching process The second production method may include a stretching step of stretching at least one of the polyimide precursor resin coating film and the imidized coating film obtained by imidizing the polyimide precursor resin coating film. When the stretching step is included, it is preferable to include a step of stretching the imidized coating film in order to improve the surface hardness of the polyimide film. The stretching step can be the same as the stretching step in the first production method.

[0135] 6. Uses of polyimide film The use of the polyimide film of the present invention is not particularly limited, and it can be used as a member such as a substrate or a surface material where glass products such as thin plate glass have been used in the past. The polyimide film of the present invention is unlikely to cause air bubble defects even if it has a thickness of 30 μm or more, and has good bending resistance, so that it can be suitably used, among others, as a display member that can accommodate curved surfaces. Specifically, the polyimide film of the present invention can be suitably used as a substrate or surface material for flexible displays, such as thin, bendable, flexible-type organic EL displays, mobile terminals such as smartphones and wristwatch-type terminals, display devices inside automobiles, flexible panels used in wristwatches, etc. The polyimide film of the present invention can also be applied to members for image display devices such as liquid crystal displays and organic EL displays, members for touch panels, flexible printed circuit boards, members for solar cell panels such as surface protective films and substrate materials, members for optical waveguides, other semiconductor-related members, etc. The laminates can also be used for the above-mentioned applications as laminates of resin layers having various other functions and polyimide films, laminates of thin glass substrates and polyimide films, and laminates of metal foils and polyimide films, as described below. Applications of metal foil and polyimide film laminates include antennas, wiring, and electromagnetic wave shielding materials.

[0136] II. Laminate II-1. First laminate The first laminate of the present invention is a laminate having the above-mentioned polyimide film of the present invention and a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound. Here, the term "hard coat layer" refers to a layer for improving surface hardness, and specifically refers to a layer that exhibits a hardness of "H" or higher in the pencil hardness test specified in JIS 5600-5-4 (1999). The first laminate of the present invention uses the polyimide film of the present invention described above, and therefore has a good appearance with suppressed air bubble defects and good bending resistance. Furthermore, since it has a hard coat layer, it is a film or resin film with improved surface hardness.

[0137] 1. Polyimide film As the polyimide film used in the laminate of the present invention, the polyimide film of the present invention described above can be used, and therefore the description thereof will be omitted here.

[0138] 2.Hard coat layer The hard coat layer used in the laminate of the present invention contains at least one polymer of a radical polymerizable compound and a cationic polymerizable compound, and may contain optional additives as necessary, as long as the effects of the present invention are not impaired.

[0139] [Polymer of at least one of radically polymerizable compound and cationic polymerizable compound] A polymer of at least one of a radical polymerizable compound and a cationic polymerizable compound can be obtained by polymerizing at least one of a radical polymerizable compound and a cationic polymerizable compound by a known method, using a polymerization initiator as necessary.

[0140] (At least one of radically polymerizable compound and cationic polymerizable compound) The radical polymerizable compound is a compound having a radical polymerizable group. The radical polymerizable group of the radical polymerizable compound is not particularly limited as long as it is a functional group capable of generating a radical polymerization reaction, and includes, for example, a group containing a carbon-carbon unsaturated double bond, and specifically includes a vinyl group, a (meth)acryloyl group, and the like. Note that, when the radical polymerizable compound has two or more radical polymerizable groups, these radical polymerizable groups may be the same or different from each other.

[0141] The number of radically polymerizable groups that the radically polymerizable compound has in one molecule is preferably 2 or more, and more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer. As the radical polymerizable compound, from the viewpoint of high reactivity, a compound having a (meth)acryloyl group is preferable. For example, polyfunctional (meth)acrylate monomers and oligomers having several (meth)acryloyl groups in a molecule and a molecular weight of several hundred to several thousand, such as urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, polyfluoroalkyl (meth)acrylate, silicone (meth)acrylate, etc., can be preferably used. Also, polyfunctional (meth)acrylate polymers having two or more (meth)acryloyl groups in the side chain of an acrylate polymer can be preferably used. Among them, polyfunctional (meth)acrylate monomers having two or more (meth)acryloyl groups in one molecule can be preferably used. By including a polymer of the polyfunctional (meth)acrylate monomer in the hard coat layer, the hardness of the hard coat layer can be improved, and further, the adhesion can be improved. Also preferably used is a polyfunctional (meth)acrylate oligomer or polymer having two or more (meth)acryloyl groups in one molecule. When the hard coat layer contains a polymerized product of the polyfunctional (meth)acrylate oligomer or polymer, the hardness and bending resistance of the hard coat layer can be improved, and further, the adhesion can be improved. In this specification, (meth)acryloyl refers to each of acryloyl and methacryloyl, and (meth)acrylate refers to each of acrylate and methacrylate.

[0142] Examples of the polyfunctional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanuric acid tri(meth)acrylate, isocyanuric acid di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, diglycerin tetra(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and those modified with PO, EO, caprolactone, etc. Among these, from the viewpoints of high reactivity, improving the hardness of the hard coat layer, and adhesion, those having 3 to 6 (meth)acryloyl groups in one molecule are preferred. For example, pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, etc. can be preferably used, and in particular, at least one selected from pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and those modified with PO, EO, or caprolactone are preferred.

[0143] In the present invention, the radical polymerizable compound may contain a monofunctional (meth)acrylate monomer in order to adjust the hardness or viscosity of the composition for the hard coat layer, improve adhesion, etc. Examples of the monofunctional (meth)acrylate monomer include hydroxyethyl acrylate (HEA), glycidyl methacrylate, methoxypolyethylene glycol (meth)acrylate, isostearyl (meth)acrylate, 2-acryloyloxyethyl succinate, acryloylmorpholine, N-acryloyloxyethylhexahydrophthalimide, cyclohexyl acrylate, tetrahydrofuryl acrylate, isobornyl acrylate, phenoxyethyl acrylate, and adamantyl acrylate.

[0144] The cationic polymerizable compound is a compound having a cationic polymerizable group. The cationic polymerizable group of the cationic polymerizable compound is not particularly limited as long as it is a functional group capable of generating cationic polymerization reaction, and examples thereof include an epoxy group, an oxetanyl group, and a vinyl ether group. Note that, when the cationic polymerizable compound has two or more cationic polymerizable groups, these cationic polymerizable groups may be the same or different from each other.

[0145] The number of cationically polymerizable groups that the cationically polymerizable compound has in one molecule is preferably 2 or more, and more preferably 3 or more, from the viewpoint of improving the hardness of the hard coat layer. Among the cationic polymerizable compounds, compounds having at least one of epoxy and oxetanyl groups as cationic polymerizable groups are preferred, and compounds having at least two of epoxy and oxetanyl groups in one molecule are more preferred. Cyclic ether groups such as epoxy and oxetanyl groups are preferred because they cause less shrinkage during polymerization. Compounds having epoxy groups among cyclic ether groups have the advantage that compounds with various structures are easily available, they do not adversely affect the durability of the obtained hard coat layer, and the compatibility with radical polymerizable compounds is easily controlled. Among cyclic ether groups, oxetanyl groups have the advantage of having a higher degree of polymerization and lower toxicity than epoxy groups, and when the obtained hard coat layer is combined with a compound having an epoxy group, it has the advantage of accelerating the network formation rate obtained from the cationic polymerizable compound in the coating film, and forming an independent network without leaving unreacted monomers in the film even in the region where it is mixed with the radical polymerizable compound.

[0146] Examples of the cationically polymerizable compound having an epoxy group include alicyclic epoxy resins obtained by epoxidizing a polyglycidyl ether of a polyhydric alcohol having an alicyclic ring or a compound containing a cyclohexene ring or a cyclopentene ring with a suitable oxidizing agent such as hydrogen peroxide or a peracid; aliphatic epoxy resins such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts, polyglycidyl esters of aliphatic long-chain polybasic acids, and homopolymers and copolymers of glycidyl (meth)acrylate; glycidyl ethers produced by reacting bisphenols such as bisphenol A, bisphenol F, and hydrogenated bisphenol A, or derivatives thereof such as alkylene oxide adducts or caprolactone adducts, with epichlorohydrin, and novolak epoxy resins, and the like, which are derived from bisphenols.

[0147] Examples of the alicyclic epoxy resin include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (UVR-6105, UVR-6107, UVR-6110) and bis-3,4-epoxycyclohexylmethyl adipate (UVR-6128) (the names in parentheses are trade names, manufactured by Dow Chemical).

[0148] In addition, the above-mentioned glycidyl ether type epoxy resins include sorbitol polyglycidyl ether (Denacol EX-611, Denacol EX-612, Denacol EX-614, Denacol EX-614B, Denacol EX-622), polyglycerol polyglycidyl ether (Denacol EX-512, Denacol EX-521), pentaerythritol polyglycidyl ether (Denacol EX-411), diglycerol polyglycidyl ether (Denacol EX-421), glycerol polyglycidyl ether (Denacol EX- 313, Denacol EX-314), trimethylolpropane polyglycidyl ether (Denacol EX-321), resorcinol diglycidyl ether (Denacol EX-201), neopentyl glycol diglycidyl ether (Denacol EX-211), 1,6-hexanediol diglycidyl ether (Denacol EX-212), hydrodibisphenol A diglycidyl ether (Denacol EX-252), ethylene glycol diglycidyl ether (Denacol EX-810, Denacol EX-811), polyethylene glycol Coal diglycidyl ether (Denacol EX-850, Denacol EX-851, Denacol EX-821), propylene glycol glycidyl ether (Denacol EX-911), polypropylene glycol glycidyl ether (Denacol EX-941, Denacol EX-920), allyl glycidyl ether (Denacol EX-111), 2-ethylhexyl glycidyl ether (Denacol EX-121), phenyl glycidyl ether (Denacol EX-141), phenol glycidyl ether (Denacol EX-145) , butylphenyl glycidyl ether (Denacol EX-146), diglycidyl phthalate (Denacol EX-721), hydroquinone diglycidyl ether (Denacol EX-203), diglycidyl terephthalate (Denacol EX-711), glycidyl phthalimide (Denacol EX-731), dibromophenyl glycidyl ether (Denacol EX-147), dibromoneopentyl glycol diglycidyl ether (Denacol EX-221) (the names in parentheses are product names, manufactured by Nagase ChemteX). Other commercially available epoxy resins may also be used.

[0149] Examples of cationic polymerizable compounds having an oxetanyl group include 3-ethyl-3-hydroxymethyloxetane (OXT-101), 1,4-bis-3-ethyloxetan-3-ylmethoxymethylbenzene (OXT-121), bis-1-ethyl-3-oxetanyl methyl ether (OXT-221), 3-ethyl-3-2-ethylhexyloxymethyloxetane (OXT-212), 3-ethyl-3-phenoxymethyloxetane (OXT-211) (all of the above, the names in parentheses are trade names, manufactured by Toa Gosei), and products under the trade names Etanacol EHO, Etanacol OXBP, Etanacol OXTP, and Etanacol OXMA (all of the above are trade names, manufactured by Ube Industries).

[0150] (Polymerization initiator) The polymer of at least one of the radical polymerizable compound and the cationic polymerizable compound contained in the hard coat layer used in the present invention can be obtained, for example, by adding a polymerization initiator to at least one of the radical polymerizable compound and the cationic polymerizable compound, if necessary, and polymerizing the compound by a known method.

[0151] The polymerization initiator can be appropriately selected from radical polymerization initiators, cationic polymerization initiators, radical and cationic polymerization initiators, etc. These polymerization initiators are decomposed by at least one of light irradiation and heating to generate radicals or cations, thereby promoting radical polymerization and cationic polymerization. Therefore, there are cases where the polymerization initiator is completely decomposed and does not remain in the hard coat layer.

[0152] The radical polymerization initiator may be any one that can release a substance that initiates radical polymerization by at least one of light irradiation and heating. For example, examples of the photoradical polymerization initiator include imidazole derivatives, bisimidazole derivatives, N-arylglycine derivatives, organic azide compounds, titanocenes, aluminate complexes, organic peroxides, N-alkoxypyridinium salts, and thioxanthone derivatives. More specifically, examples of the photoradical polymerization initiator include 1,3-di(tert-butyldioxycarbonyl)benzophenone, 3,3',4,4'-tetrakis(tert-butyldioxycarbonyl)benzophenone, 3-phenyl-5-isoxazolone, 2-mercaptobenzimidazole, bis(2,4,5-triphenyl)imidazole, 2,2-dimethoxy-1,2-diphenyl Examples of suitable phenylethane-1-one (trade name Irgacure 651, manufactured by Ciba Japan Co., Ltd.), 1-hydroxy-cyclohexyl-phenyl-ketone (trade name Irgacure 184, manufactured by Ciba Japan Co., Ltd.), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one (trade name Irgacure 369, manufactured by Ciba Japan Co., Ltd.), bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium) (trade name Irgacure 784, manufactured by Ciba Japan Co., Ltd.), but are not limited thereto. In addition to the above, commercially available products can be appropriately selected and used.

[0153] The cationic polymerization initiator may be any one that can release a substance that initiates cationic polymerization by at least one of light irradiation and heating. Examples of cationic polymerization initiators include sulfonic acid esters, imide sulfonates, dialkyl-4-hydroxysulfonium salts, arylsulfonic acid-p-nitrobenzyl esters, silanol-aluminum complexes, (η 6 -benzene)(η 5 -cyclopentadienyl)iron(II), and more specific examples include benzoin tosylate, 2,5-dinitrobenzyl tosylate, N-tosylated phthalimide, and the like, but are not limited to these.

[0154] Examples of initiators that can be used both as radical polymerization initiators and as cationic polymerization initiators include aromatic iodonium salts, aromatic sulfonium salts, aromatic diazonium salts, aromatic phosphonium salts, triazine compounds, and iron arene complexes. More specifically, examples of initiators that can be used both as radical polymerization initiators and as cationic polymerization initiators include iodonium salts such as diphenyliodonium, ditolyliodonium, bis(p-tert-butylphenyl)iodonium, bis(p-chlorophenyl)iodonium, and the like; chlorides, bromides, boron fluorides, hexafluorophosphate salts, and hexafluoroantimonate salts of iodonium; triphenylsulfonium, Examples of the sulfonium salts include sulfonium chlorides, bromides, boron fluorides, hexafluorophosphate salts, hexafluoroantimonate salts, etc., of 4-tert-butyltriphenylsulfonium and tris(4-methylphenyl)sulfonium, and 2,4,6-substituted-1,3,5-triazine compounds such as 2,4,6-tris(trichloromethyl)-1,3,5-triazine, 2-phenyl-4,6-bis(trichloromethyl)-1,3,5-triazine, and 2-methyl-4,6-bis(trichloromethyl)-1,3,5-triazine, but are not limited to these.

[0155] (Optional addition ingredient) The hard coat layer used in the present invention may further contain optional additive components in addition to the polymer, if necessary. The optional added components are appropriately selected depending on the function to be imparted to the hard coat layer, and are not particularly limited. Examples of the optional added components include inorganic or organic fine particles for adjusting the hardness or refractive index, ultraviolet absorbers, infrared absorbers, antiglare agents, antifouling agents, antistatic agents, and the like. Furthermore, the optional added components may include leveling agents, surfactants, lubricants, various sensitizers, flame retardants, adhesion promoters, polymerization inhibitors, antioxidants, surface modifiers, and the like.

[0156] At least one polymer of the radical polymerizable compound and the cationic polymerizable compound contained in the hard coat layer used in the present invention can be analyzed using a Fourier transform infrared spectrophotometer (FTIR) or a pyrolysis gas chromatograph (GC-MS), and decomposition products of the polymer can be analyzed using a combination of high performance liquid chromatography, a gas chromatograph mass spectrometer, NMR, elemental analysis, XPS / ESCA, TOF-SIMS, etc.

[0157] 3.Laminate structure The first laminate of the present invention is not particularly limited as long as it has the polyimide film and the hard coat layer, and may be one in which the hard coat layer is laminated on one side of the polyimide film, or one in which the hard coat layer is laminated on both sides of the polyimide film. From the viewpoint of impact resistance, the laminate of the present invention may contain two or more layers of the polyimide film, for example, a composite film in which two of the polyimide films are laminated with an adhesive layer. In addition, the first laminate of the present invention may have, in addition to the polyimide film and the hard coat layer, other layers such as a primer layer for improving the adhesion between the polyimide film and the hard coat layer, and the polyimide film and the hard coat layer may be laminated via other layers such as a primer layer, as long as the effects of the present invention are not impaired. In addition, the first laminate of the present invention may have the polyimide film and the hard coat layer adjacent to each other. In addition, the first laminate of the present invention may further have an impact-resistant layer, a fingerprint-proof layer, an adhesive or pressure-sensitive adhesive layer, etc. As the other conventionally known functional layers such as the primer layer, impact resistant layer, fingerprint prevention layer, adhesive or pressure sensitive adhesive layer, any conventionally known layer can be appropriately selected and used. Alternatively, the first laminate of the present invention may further include a metal foil. In the first laminate of the present invention, the adhesive layer and the primer layer may contain a colorant in order to adjust the YI. Moreover, in order to adjust the transmittance, the first laminate of the present invention may further have a layer having a refractive index lower than that of the polyimide film on the side of the polyimide film on which the hard coat layer is not formed, and the low refractive index layer may contain inorganic fine particles, and further, in order to adjust the YI, may contain a colorant including a blue dye or a purple dye.

[0158] The total thickness of the first laminate of the present invention may be appropriately selected depending on the application, but from the viewpoint of strength, it is preferably 10 μm or more, more preferably 40 μm or more, and from the viewpoint of bending resistance, it is preferably 300 μm or less, more preferably 250 μm or less.

[0159] 4. Properties of the laminate In the first laminate of the present invention, the pencil hardness of the surface on the hard coat layer side is preferably H or more, more preferably 2H or more, and even more preferably 3H or more. The pencil hardness of the first laminate of the present invention can be measured in the same manner as in the method for measuring the pencil hardness of the polyimide film, except that the load is 9.8 N.

[0160] The first laminate of the present invention has a total light transmittance measured in accordance with JIS K7361-1 of preferably 85.0% or more, more preferably 88.0% or more, and even more preferably 90.0% or more. Such a high transmittance results in good transparency, and the laminate can be used as a substitute for glass. The total light transmittance of the first laminate of the present invention can be measured in the same manner as the total light transmittance of the polyimide film, which is measured in accordance with JIS K7361-1.

[0161] The first laminate of the present invention preferably has a yellowness index (YI value) calculated in accordance with JIS K7373-2006 of 10.0 or less, more preferably 7.0 or less, even more preferably 5.0 or less, and particularly preferably 3.0 or less. Furthermore, since the first laminate of the present invention is suppressed from yellowing, has improved light transmittance, and can be suitably used as a glass substitute material, the yellowness index (YI value) calculated in accordance with JIS K7373-2006 is preferably 0.3 or less, more preferably 0.14 or less, and even more preferably 0.06 or less, divided by the total film thickness (μm) of the polyimide film and the hard coat layer (YI value / film thickness (μm)). The yellowness index (YI value) of the first laminate of the present invention can be measured in the same manner as the yellowness index (YI value) of the polyimide film calculated in accordance with JIS K7373-2006.

[0162] The haze value of the first laminate of the present invention may be 2.0 or less, more preferably 1.0 or less, and even more preferably 0.5 or less, from the viewpoint of light transmittance. The haze value of the first laminate of the present invention can be measured in the same manner as the haze value of the polyimide film.

[0163] 5. Applications of laminates The use of the first laminate of the present invention is not particularly limited, and it can be used, for example, in the same applications as those of the polyimide film of the present invention described above.

[0164] 6. Manufacturing method of laminate The first method for producing the laminate of the present invention may, for example, be forming a coating film of a composition for forming a hard coat layer, which contains at least one of a radical polymerizable compound and a cationic polymerizable compound, on at least one surface of the polyimide film of the present invention; and curing the coating film.

[0165] The composition for forming a hard coat layer contains at least one of a radically polymerizable compound and a cationic polymerizable compound, and may further contain a polymerization initiator, a solvent, an additive, and the like, as necessary. Here, the radical polymerizable compound, cationic polymerizable compound, polymerization initiator, and additives contained in the hard coat layer-forming composition can be the same as those described in the hard coat layer, and the solvent can be appropriately selected from known solvents.

[0166] As a method for forming a coating film of the composition for forming a hard coat layer on at least one surface of a polyimide film, for example, a method of coating the composition for forming a hard coat layer on at least one surface of a polyimide film by a known coating means can be mentioned. The coating means is not particularly limited as long as it is a method capable of coating with a desired film thickness, and examples thereof include the same means as those for coating the polyimide varnish onto the support.

[0167] The coating film of the curable resin composition for hard coat layer is dried as necessary to remove the solvent. Examples of the drying method include drying under reduced pressure, drying by heating, and a combination of these drying methods. When drying is performed under normal pressure, it is preferable to dry at 30°C or higher and 110°C or lower.

[0168] The hard coat layer curable resin composition is applied to a coating film, which is dried as necessary, and then the coating film is cured by at least one of light irradiation and heating depending on the polymerizable groups of the radical polymerizable compound and the cationic polymerizable compound contained in the curable resin composition, thereby forming a hard coat layer containing at least one polymer of a radical polymerizable compound and a cationic polymerizable compound on at least one surface of a polyimide film.

[0169] For light irradiation, ultraviolet light, visible light, electron beams, ionizing radiation, etc. are mainly used. For ultraviolet curing, ultraviolet light emitted from light beams of ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arcs, xenon arcs, metal halide lamps, etc. are used. The irradiation dose of the energy ray source is 50 to 5000 mJ / cm as the cumulative exposure dose at an ultraviolet wavelength of 365 nm. 2 That's about it. When heating is performed, the treatment is usually performed at a temperature of 40° C. or higher and 120° C. or lower. Alternatively, the reaction may be performed by leaving the mixture at room temperature (25° C.) for 24 hours or more.

[0170] II-2. Second laminate The second laminate of the present invention is a laminate having a glass substrate having a thickness of 100 μm or less and the above-mentioned polyimide film of the present invention. The second laminate of the present invention is a laminate of the polyimide film of the present invention on a flexible glass substrate having a thickness of 100 μm or less, and therefore can be regarded as a replacement of a part of the thickness of a conventional glass substrate with the polyimide film of the present invention. As glass becomes thinner, it becomes more fragile and its impact resistance is dramatically deteriorated, but the second laminate of the present invention has the advantages of the hardness and optical properties of the glass substrate, while suppressing the cracking of the glass substrate and improving its impact resistance. The second laminate of the present invention is a laminate of the polyimide film of the present invention on a flexible glass substrate having a thickness of 100 μm or less, and therefore has excellent surface hardness and impact resistance, suppresses bubble defects, provides a good appearance, and has good bending resistance. The second laminate of the present invention is also preferable in that it is less likely to develop a crease because it has a glass substrate having a thickness of 100 μm or less.

[0171] 1. Polyimide film The thickness of the polyimide film used in the second laminate of the present invention may be appropriately selected, but is preferably 5 μm to 60 μm, more preferably 10 μm to 50 μm, and even more preferably 15 μm to 40 μm. By making the thickness of the polyimide film relatively thin within the above range, the flexibility of the second laminate can be increased while suppressing cracking of the glass substrate, and bending resistance can be improved. As the polyimide film, the polyimide film of the present invention described above can be used, and therefore the description thereof will be omitted here.

[0172] 2. Glass substrate The glass substrate in the second laminate of the present invention has a thickness of 100 μm or less. The glass constituting the glass substrate is not particularly limited, but among them, chemically strengthened glass is preferable from the viewpoint of bending resistance. Chemically strengthened glass is preferable because it has excellent mechanical strength and can be made thinner accordingly. Chemically strengthened glass is typically glass whose mechanical properties are strengthened by a chemical method by partially exchanging ion species, such as replacing sodium with potassium, near the surface of the glass, and has a compressive stress layer on the surface.

[0173] Examples of glasses constituting the chemically strengthened glass substrate include aluminosilicate glass, soda lime glass, borosilicate glass, lead glass, alkali barium glass, and aluminoborosilicate glass.

[0174] Commercially available chemically strengthened glass substrates include, for example, Gorilla Glass from Corning and Dragontrail from AGC. In addition, as the chemically strengthened glass substrate, for example, those described in JP 2019-194143 A can also be used.

[0175] The thickness of the glass substrate is 100 μm or less, preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 90 μm or less, and even more preferably 25 μm or more and 80 μm or less. By making the thickness of the glass substrate thin in the above range, good flexibility can be obtained and sufficient hardness can be obtained. In addition, curling of the laminate can be suppressed. Furthermore, it is preferable in terms of reducing the weight of the laminate.

[0176] 3.Laminate structure The second laminate of the present invention is not particularly limited as long as it has the glass substrate and the polyimide film, and may be one in which the polyimide film is laminated on one side of the glass substrate, or may be one in which the polyimide film is laminated on both sides of the glass substrate. In addition to the glass substrate and the polyimide film, the second laminate of the present invention may have other layers such as a primer layer for improving the adhesion between the glass substrate and the polyimide film, as long as the effect of the present invention is not impaired, and the glass substrate and the polyimide film may be laminated via other layers such as a primer layer. In addition, the second laminate of the present invention may be one in which the glass substrate and the polyimide film are adjacent to each other. In addition, the second laminate of the present invention may further have a hard coat layer, an impact-resistant layer, a fingerprint prevention layer, an adhesive or adhesive layer, a protective layer, etc., as described in the first laminate. The primer layer, impact-resistant layer, fingerprint-preventing layer, adhesive or pressure-sensitive adhesive layer, protective layer, and the like may each have a conventionally known structure.

[0177] The total thickness of the second laminate of the present invention may be appropriately selected depending on the application, but from the viewpoint of strength, it is preferably 20 μm or more, more preferably 40 μm or more, and from the viewpoint of bending resistance, it is preferably 300 μm or less, more preferably 250 μm or less.

[0178] 4. Properties of the laminate The second laminate of the present invention also preferably has properties such as pencil hardness, total light transmittance, yellowness index, and haze value similar to those of the first laminate of the present invention. In addition, the second laminate of the present invention preferably has a composite elastic modulus of 5.5 GPa or more of the laminated polyimide film. In this way, when the composite elastic modulus of the polyimide film is high, the film can maintain a sufficient surface hardness as a protective film even at room temperature, and can be used as a surface material or a substrate. The composite elastic modulus is more preferably 5.7 GPa or more, even more preferably 6.0 GPa or more, and even more preferably 6.3 GPa or more. On the other hand, the composite elastic modulus may be 10 GPa or less from the viewpoint of improving bending resistance. The composite elastic modulus of the polyimide film laminated on the second laminate can be measured by the method described in the Examples section below.

[0179] In the polyimide film in the second laminate of the present invention, the content of dichloromethane is preferably 1000 ppm or less, more preferably 800 ppm or less, even more preferably 400 ppm or less, and even more preferably 100 ppm or less, from the viewpoint of improving bending resistance or preventing long-term deterioration of optical properties, in the polyimide film in the second laminate of the present invention, the content of an organic solvent having a boiling point of 70° C. or more, particularly 100° C. or more, at 1 atmospheric pressure is preferably 1000 ppm or less, more preferably 800 ppm or less, even more preferably 400 ppm or less, and even more preferably 100 ppm or less. The amount of residual solvent in the polyimide film in the second laminate can be measured in the same manner as the amount of residual solvent in the polyimide film, by peeling off the polyimide film from the laminate.

[0180] The polyimide film in the second laminate of the present invention also preferably has few air bubble defects. 2 Preferably, the number of bubble defects per unit area is less than 1, more preferably 0.7 or less, and even more preferably 0.5 or less. The number of bubble defects per unit area can be determined by the method described in the Examples section below.

[0181] 5. Applications of laminates The use of the second laminate of the present invention is not particularly limited, and for example, it can be used in the same applications as those of the polyimide film of the present invention described above.

[0182] 6. Manufacturing method of laminate Examples of the method for producing the second laminate of the present invention include a method of applying a polyimide varnish containing the specific polyimide and an organic solvent onto the glass substrate and drying the same, and a method of applying a polyimide precursor composition containing a polyimide precursor (polyamic acid) and an organic solvent onto the glass substrate, and then imidizing the polyimide precursor by heat treatment.

[0183] Among these, the following production method is preferred because it is less likely to cause bubble defects and makes it easier to obtain a laminate having good thickness uniformity. The second method for producing a laminate of the present invention includes the steps of: Providing the glass substrate; A step of preparing a polyimide varnish containing the polyimide used in the present invention and an organic solvent, the polyimide content in the polyimide varnish being 6% by mass or more and 15% by mass or less, and having a viscosity of 1,000 to 10,000 cps at 25°C as measured by a rotational viscometer; It is preferable to have a step of applying the polyimide varnish onto the glass substrate, a first drying step of drying the coating film at a temperature of 100°C or less, and a second drying step of heating the dried coating film at a temperature of 150°C or more, since this makes it difficult for air bubble defects to occur and makes it easy to reduce the amount of residual solvent.

[0184] In particular, when an organic solvent having a boiling point of 120° C. or higher is used, it is preferable to dry the organic solvent by setting two or more drying temperature stages at a temperature of 100° C. or lower, since this can suppress skinning on the coating film surface and suppress bubbles due to bumping of the organic solvent in the coating film. An example of an embodiment having two or more drying temperature stages at a temperature of 100° C. or lower is an embodiment in which the first stage is drying at 80° C. and the second stage is further drying at 100° C. In addition, the heating at 150° C. or higher in the second drying step is preferably performed at two or more heating temperatures between 150° C. and 250° C., since this makes it difficult for bubble defects to occur and makes it easy to reduce the amount of residual solvent. An example of a mode in which two or more heating temperatures are performed at a temperature between 150° C. and 250° C. is a mode in which the first stage is drying at 150° C., the second stage is drying at 180° C., the third stage is drying at 230° C., and the fourth stage is further drying at 250° C. For example, when the thickness of the coating film after drying is less than 50 μm, it is preferable that the holding time at each stage be 10 minutes or more and less than 60 minutes, and when the thickness of the coating film after drying is 50 μm or more and 100 μm or less, it is preferable that the holding time at each stage be 30 minutes or more and less than 90 minutes.

[0185] III. Display components The display member of the present invention includes the polyimide film of the present invention or the laminate of the present invention. Examples of the display member of the present invention include a surface material for a display and a base material for a display. The display member of the present invention may be the polyimide film of the present invention or the laminate of the present invention.

[0186] The display member of the present invention is used, for example, as a display surface material by being disposed on the surface of various displays. Like the polyimide film of the present invention and the laminate of the present invention described above, the display member of the present invention is less likely to develop air bubble defects, has good transparency, and has improved bending resistance, and is therefore particularly suitable for use in flexible displays.

[0187] The display member of the present invention can be used in various known displays, and is not particularly limited. For example, it can be used in the displays described above in the applications of the polyimide film of the present invention.

[0188] In addition, when the display member of the present invention is the laminate of the present invention, the surface that becomes the outermost surface after the laminate is placed on the surface of the display may be the surface on the polyimide film side or the surface on the hard coat layer side. In particular, it is preferable to place the display member of the present invention so that the surface on the hard coat layer side becomes the outermost surface. In addition, the display member of the present invention may have a fingerprint adhesion prevention layer on the outermost surface.

[0189] The method for disposing the display member of the present invention on the surface of a display is not particularly limited, but may be, for example, a method via an adhesive layer, etc. As the adhesive layer, a conventionally known adhesive layer that can be used for adhering display members can be used.

[0190] IV. Touch panel components The touch panel member of the present invention comprises the polyimide film of the present invention or the laminate of the present invention described above, a transparent electrode including a plurality of conductive portions disposed on one surface side of the polyimide film or the laminate; and a plurality of lead wires electrically connected to at least one end of the conductive portion.

[0191] Since the touch panel member of the present invention comprises the polyimide film or laminate of the present invention described above, it has excellent bending resistance and is particularly suitable for use in flexible displays, and also has excellent optical properties. The laminate of the present invention used in the touch panel member of the present invention preferably has a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound adjacent to both sides of the polyimide film. Furthermore, although there is no particular limitation, the touch panel member of the present invention is preferably one in which the transparent electrode is laminated in contact with one surface side of the laminate. The touch panel member of the present invention can be used, for example, by being disposed on the surface of various displays. Also, the touch panel member of the present invention and the polyimide film or laminate of the present invention as a surface material can be disposed in this order on the surface of various displays.

[0192] Hereinafter, the touch panel member of the present invention will be described using an example in which the laminate of the present invention described above is used. However, the polyimide film of the present invention described above can also be used in place of the laminate of the present invention described above. FIG. 3 is a schematic plan view of one surface of an example of the touch panel member of the present invention, FIG. 4 is a schematic plan view of the other surface of the touch panel member shown in FIG. 3, and FIG. 5 is an A-A' cross-sectional view of the touch panel member shown in FIG. 3 and FIG. 4. The touch panel member 20 shown in FIG. 3, FIG. 4, and FIG. 5 includes the laminate 10 of the present invention, a first transparent electrode 4 arranged in contact with one surface of the laminate 10, and a second transparent electrode 5 arranged in contact with the other surface of the laminate 10. In the first transparent electrode 4, a plurality of first conductive parts 41, which are strip-shaped electrode pieces extending so as to extend in the x-axis direction, are arranged at predetermined intervals. A first lead wire 7 electrically connected to the first conductive part 41 is connected to the first conductive part 41 at one of its longitudinal ends. It is preferable to provide a first terminal 71 for electrically connecting to an external circuit at an end of the first lead wire 7 extended to the edge 21 of the laminate 10. The first conductive portion 41 and the first lead wire 7 are generally connected within a non-active area 23 located outside an active area 22 that is visible to a user of the touch panel. 3, a connection structure in which a connection portion 24 is interposed between the first conductive portion 41 and the first output wire 7 can be adopted. Specifically, the connection portion 24 can be formed by extending a layer of a conductive material from a longitudinal end of the first conductive portion 41 to a predetermined position in the inactive area 23. Furthermore, by overlapping at least a portion of the first output wire 7 on the connection portion 24, a connection structure between the first conductive portion 41 and the first output wire 7 can be formed. The connection between the first conductive portion 41 and the first lead wire 7 is not limited to the structure forming the connection portion 24 as shown in Fig. 3. For example, although not shown, the longitudinal end of the first conductive portion 41 may be extended to the inactive area 23, and the first lead wire 7 may be caused to ride up onto the end of the first conductive portion 41 that has been extended to the inactive area 23 within the inactive area 23, thereby electrically connecting the two. In addition, Figure 3 shows a configuration in which one of the longitudinal ends of the first conductive portion 41 is connected to the first output wire 7, but in the present invention, the first output wire 7 may be electrically connected to both longitudinal ends of one first conductive portion 41, respectively.

[0193] 4, the touch panel component 20 includes a second transparent electrode 5 arranged in contact with the other surface of the laminate 10. In the second transparent electrode 5, second conductive portions 51, which are multiple rectangular electrode pieces extending in the y-axis direction, are arranged at predetermined intervals in the x-axis direction. A second output wire 8 that is electrically connected to the second conductive portion 51 is connected to one of the longitudinal ends of the second conductive portion 51 . The second output wire 8 is extended to a position on the edge 21 of the laminate 10 to which the above-mentioned first output wire 7 is extended, so as not to overlap with the first terminal 71 . At the end of the second output wire 8 extending to the edge 21 of the laminate 10, a second terminal 81 for electrical connection to an external circuit is preferably provided. The electrical connection between the second conductive portion 51 and the second output wire 8 can be made in the same manner as the electrical connection between the first output wire 7 and the first conductive portion 41 .

[0194] 3 and 4, the pattern in which the first output wire 7 is a long wire and the second output wire 8 is a short wire is merely one embodiment of the touch panel member of the present invention, and it is also possible to use a pattern in which the first output wire 7 is a short wire and the second output wire 8 is a long wire. Furthermore, the extension directions of the first output wire 7 and the second output wire 8 are not limited to the directions shown in Figs. 3 and 4, and can be designed arbitrarily.

[0195] The conductive portion of the touch panel member of the present invention can be appropriately selected from those constituting the transparent electrode in the touch panel member, and the pattern of the conductive portion is not limited to those shown in Figures 3 and 4. For example, a transparent electrode pattern capable of detecting a change in capacitance due to contact or near-contact with a finger or the like by a capacitance method can be appropriately selected and applied. The material of the conductive portion is preferably a light-transmitting material, and examples thereof include, but are not limited to, indium oxide-based transparent electrode materials mainly composed of indium tin oxide (ITO), indium oxide, indium zinc oxide (IZO), etc., transparent conductive films mainly composed of tin oxide (SnO2), zinc oxide (ZnO), etc., conductive polymer compounds such as polyaniline and polyacetylene, etc. In addition, the first conductive portion 41 and the second conductive portion 51 may be formed using the same type of conductive material, or may be formed using different types of materials. In particular, it is preferable to form the first conductive portion 41 and the second conductive portion 51 using the same type of conductive material in terms of more effectively suppressing the occurrence of warping and distortion of the touch panel member. The thickness of the conductive portion is not particularly limited, but when the conductive portion is formed by photolithography, for example, it can generally be formed to be about 10 nm to 500 nm.

[0196] The conductive material constituting the take-out wire of the touch panel member of the present invention may or may not have optical transparency. In general, the take-out wire can be formed using a metal material such as silver or copper having high electrical conductivity. Specifically, examples of the take-out wire include a metal element, a metal complex, a complex of a metal and a metal compound, and a metal alloy. Examples of the metal element include a metal element such as silver, copper, gold, chromium, platinum, or aluminum. Examples of the metal complex include MAM (a three-layer structure of molybdenum, aluminum, and molybdenum). Examples of the complex of a metal and a metal compound include a laminate of chromium oxide and chromium. Examples of the metal alloy include silver alloy and copper alloy. Examples of the metal alloy include APC (an alloy of silver, palladium, and copper). In addition, the take-out wire may include the above-mentioned metal material mixed with an appropriate resin component. In the touch panel member of the present invention, the terminals provided at the ends of the extraction lines can be formed, for example, using the same material as the extraction lines. The thickness and width of the take-out wire are not particularly limited, but for example, when the take-out wire is formed by a photolithography method, the thickness is generally about 10 nm to 1000 nm, and the width is generally about 5 μm to 200 μm. On the other hand, when the take-out wire is formed by printing such as screen printing, the thickness is generally about 5 μm to 20 μm, and the width is generally about 20 μm to 300 μm.

[0197] The touch panel member of the present invention is not limited to the forms shown in Figures 3 to 5, and may be configured, for example, by stacking a first transparent electrode and a second transparent electrode on separate laminates. 6 and 7 are schematic plan views each showing an example of a conductive member including a laminate of the present invention. A first conductive member 201 shown in Fig. 6 has a laminate 10 of the present invention and a first transparent electrode 4 arranged in contact with one surface of the laminate 10, and the first transparent electrode 4 has a plurality of first conductive parts 41. A second conductive member 202 shown in Fig. 7 has a laminate 10' of the present invention and a second transparent electrode 5 arranged in contact with one surface of the laminate 10', and the second transparent electrode 5 has a plurality of second conductive parts 51. FIG. 8 is a schematic cross-sectional view showing another example of the touch panel member of the present invention. The touch panel member 20' shown in FIG. 8 includes the first conductive member 201 shown in FIG. 6 and the second conductive member 202 shown in FIG. 7. In the touch panel member 20', the surface of the first conductive member 201 that does not have the first transparent electrode 4 and the surface of the second conductive member 202 that has the transparent electrode 5 are bonded together via an adhesive layer 6. In the present invention, for example, as an adhesive layer for bonding the laminate of the present invention and the touch panel member of the present invention, an adhesive layer for bonding the touch panel members of the present invention to each other, and an adhesive layer for bonding the touch panel member of the present invention and a display device, a conventionally known adhesive layer used in an optical member can be appropriately selected and used. In the conductive member used in the touch panel member of the present invention, the configurations and materials of the transparent electrodes, the take-out wires, and the terminals can be the same as those of the transparent electrodes, the take-out wires, and the terminals used in the touch panel member of the present invention described above.

[0198] V.Liquid crystal display device The liquid crystal display device of the present invention comprises the polyimide film of the present invention or the laminate of the present invention described above, and a liquid crystal display section having a liquid crystal layer between opposing substrates, which is arranged on one side of the polyimide film or the laminate.

[0199] The liquid crystal display device of the present invention includes the polyimide film of the present invention or the laminate of the present invention, and therefore has excellent bending resistance, can be particularly suitably used for flexible displays, and has excellent optical properties. The laminate of the present invention used in the liquid crystal display device of the present invention preferably has hard coat layers containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound adjacent to both sides of the polyimide film. The liquid crystal display device of the present invention may include the above-mentioned touch panel member of the present invention. The counter substrate of the liquid crystal display device of the present invention may include the polyimide film or laminate of the present invention.

[0200] Hereinafter, the liquid crystal display device of the present invention will be described using an example in which the laminate of the present invention described above is used. However, the polyimide film of the present invention described above can also be used in place of the laminate of the present invention described above. Fig. 9 is a schematic cross-sectional view showing one example of a liquid crystal display device of the present invention. The liquid crystal display device 100 shown in Fig. 9 comprises a laminate 10 of the present invention, a touch panel member 20 having a first transparent electrode 4 on one surface of the laminate 10' of the present invention and a second transparent electrode 5 on the other surface, and a liquid crystal display unit 30. In the liquid crystal display device 100, the laminate 10 is used as a surface material, and the laminate 10 and the touch panel member 20 are bonded together via an adhesive layer 6.

[0201] The liquid crystal display section used in the liquid crystal display device of the present invention has a liquid crystal layer formed between substrates arranged opposite each other, and can adopt a configuration used in conventionally known liquid crystal display devices. The driving method for the liquid crystal display device of the present invention is not particularly limited, and any driving method generally used for liquid crystal display devices can be adopted, such as the TN method, the IPS method, the OCB method, and the MVA method. The counter substrate used in the liquid crystal display device of the present invention can be appropriately selected depending on the driving method of the liquid crystal display device, and may include the polyimide film or laminate of the present invention. As the liquid crystal constituting the liquid crystal layer, various liquid crystals with different dielectric anisotropy and mixtures of these can be used depending on the driving method of the liquid crystal display device of the present invention. The liquid crystal layer can be formed by a method generally used for producing liquid crystal cells, such as a vacuum injection method, a liquid crystal dropping method, etc. After the liquid crystal layer is formed by the above method, the liquid crystal cell is gradually cooled to room temperature, whereby the enclosed liquid crystal can be aligned. In the liquid crystal display device of the present invention, a colored layer of multiple colors or a light-shielding portion for defining pixels may be further provided between the opposing substrates. The liquid crystal display unit may have a backlight unit having light-emitting elements and phosphors on the outer side of the opposing substrates, opposite to the side where the touch panel member is located. The opposing substrates may each have a polarizing plate on their outer surfaces.

[0202] FIG. 10 is a schematic cross-sectional view showing another example of a liquid crystal display device of the present invention. A liquid crystal display device 200 shown in FIG. 10 includes the laminate 10 of the present invention, a touch panel member 20′ having a first conductive member 201 having a first transparent electrode 4 on one surface of the laminate 10′ of the present invention, and a second conductive member 202 having a second transparent electrode 5 on one surface of the laminate 10″ of the present invention, and a liquid crystal display unit 30. In the liquid crystal display device 200, the laminate 10 and the first conductive member 201, and the first conductive member 201 and the second conductive member 202 are bonded together via an adhesive layer 6. The configuration of the touch panel member 20′ can be the same as that of the touch panel member 20′ shown in FIG. 8, for example. As the conductive member used in the liquid crystal display device of the present invention, the same conductive member used in the touch panel member of the present invention can be used.

[0203] VI. Organic Electroluminescent Display Devices The organic electroluminescent display device of the present invention comprises the polyimide film of the present invention or the laminate of the present invention described above, and an organic electroluminescent display section having an organic electroluminescent layer between opposing substrates, which is arranged on one side of the polyimide film or the laminate.

[0204] The organic electroluminescent display device of the present invention includes the polyimide film of the present invention or the laminate of the present invention described above, and therefore has excellent bending resistance, and is particularly suitable for use as a flexible display, and has excellent optical properties. The laminate of the present invention used in the organic electroluminescent display device of the present invention preferably has a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound adjacent to both sides of the polyimide film. The organic electroluminescent display device of the present invention may include the above-mentioned touch panel member of the present invention. The counter substrate of the organic electroluminescent display device of the present invention may include the polyimide film or laminate of the present invention.

[0205] Fig. 11 is a schematic cross-sectional view showing one example of an organic electroluminescent display device of the present invention. The organic electroluminescent display device 300 shown in Fig. 11 has the laminate 10 of the present invention, a touch panel member 20 having a first transparent electrode 4 on one side of the laminate 10' of the present invention and a second transparent electrode 5 on the other side, and an organic electroluminescent display unit 40. In the organic electroluminescent display device 300, the laminate 10 is used as a surface material, and the laminate 10 and the touch panel member 20 are bonded together via an adhesive layer 6.

[0206] The organic electroluminescent display unit (organic EL display unit) used in the organic electroluminescent display device (organic EL display device) of the present invention has an organic electroluminescent layer (organic EL layer) formed between opposing substrates, and can have a configuration used in conventionally known organic EL display devices. The organic EL display unit may further include a support substrate, an organic EL element including an organic EL layer, an anode layer and a cathode layer sandwiching the organic EL layer, and a sealing base material sealing the organic EL element. The organic EL layer may include at least an organic EL light-emitting layer, and may include, for example, a layer having a structure in which a hole injection layer, a hole transport layer, an organic EL light-emitting layer, an electron transport layer, and an electron injection layer are laminated in this order from the anode layer side. The organic EL display device of the present invention can be applied to, for example, both passive driving organic EL displays and active driving organic EL displays. The counter substrate used in the organic EL display device of the present invention can be appropriately selected depending on the driving method of the organic EL display device, and may include the laminate of the present invention.

[0207] FIG. 12 is a schematic cross-sectional view showing another example of the organic electroluminescent display device of the present invention. The organic electroluminescent display device 400 shown in FIG. 12 has the laminate 10 of the present invention, a touch panel member 20' having a first conductive member 201 having a first transparent electrode 4 on one side of the laminate 10' of the present invention, and a second conductive member 202 having a second transparent electrode 5 on one side of the laminate 10" of the present invention, and an organic electroluminescent display unit 40. In the organic electroluminescent display device 400, the laminate 10 and the first conductive member 201, and the first conductive member 201 and the second conductive member 202 are bonded together via an adhesive layer 6. The configuration of the touch panel member 20' can be the same as that of the touch panel member 20' shown in FIG. 7, for example. As the conductive member used in the organic electroluminescent display device of the present invention, the same conductive member used in the touch panel member of the present invention can be used. EXAMPLES

[0208] [Evaluation method] Unless otherwise specified, measurements and evaluations were performed at 25°C. The film specimens were cut near the center of the film. In addition, the following Examples 12 and 29 are considered as reference examples.

[0209] <Weight average molecular weight of polyimide precursor> The weight average molecular weight of the polyimide precursor was measured by dissolving the polyimide precursor in N-methylpyrrolidone (NMP) at a concentration of 0.5% by mass, filtering the solution through a syringe filter (pore size: 0.45 μm), and using a 10 mmol% LiBr-NMP solution with a water content of 500 ppm or less as a developing solvent, using a GPC apparatus (HLC-8120 manufactured by Tosoh, column used: GPC LF-804 manufactured by SHODEX), with a sample injection amount of 50 μL, a solvent flow rate of 0.5 mL / min, and a temperature of 40 ° C. The weight average molecular weight of the polyimide precursor was measured using polystyrene standard samples (weight average molecular weights: 364,700, 204,000, 103,500, 44,360, 27,500, 13,030, 6,300, 3,070) of the same concentration as the sample as a standard polystyrene conversion value. The elution time was compared with a calibration curve to determine the weight average molecular weight.

[0210] <Weight average molecular weight of polyimide> 15 mg of polyimide powder was immersed in 15,000 mg of N-methylpyrrolidone (NMP), heated to 60 °C in a water bath, and stirred at a rotation speed of 200 rpm using a stirrer for 3 to 60 hours until dissolution was visually confirmed to obtain an NMP solution with a concentration of 0.1% by mass. The solution was filtered through a syringe filter (pore size: 0.45 μm), and a 30 mmol% LiBr-NMP solution with a water content of 500 ppm or less was used as the developing solvent. Using a GPC apparatus (manufactured by Tosoh Corporation, HLC-8120, detector: differential refractive index (RID) detector, two SHODEX GPC LF-804 columns connected in series), measurements were carried out under the conditions of a sample injection volume of 50 μL, a solvent flow rate of 0.4 mL / min, a column temperature of 37 °C, and a detector temperature of 37 °C. The weight average molecular weight of the polyimide was taken as the conversion value with respect to standard polystyrene measured based on polystyrene standard samples (weight average molecular weights: 364,700, 204,000, 103,500, 44,360, 27,500, 13,030, 6,300, 3,070) with the same concentration as the sample. The elution time was compared with the calibration curve to determine the weight average molecular weight.

[0211] <Viscosity of Polyimide Varnish> The viscosity of the polyimide varnish was measured at 25 °C with a sample volume of 50 ml using a single-cylinder rotational viscometer (e.g., TVB-10 type viscometer, M4 rotor manufactured by Toki Sangyo Co., Ltd.) according to the method described in JIS K7117-1.

[0212] <YI value (Yellowness)> The YI value was determined in accordance with JIS K7373-2006 using an ultraviolet-visible-near-infrared spectrophotometer (V-7100 manufactured by JASCO Corporation) by the spectral colorimetric method. Based on the transmittance measured at 1 nm intervals in the range of 250 nm to 800 nm using supplementary illuminant C and a 2° field of view, the tristimulus values X, Y, Z in the XYZ color system were obtained, and calculated from the following formula using the values of X, Y, Z. YI = 100(1.2769X - 1.0592Z) / Y

[0213] <Total Light Transmittance, Haze Value> The total light transmittance was measured using a haze meter (HM150 manufactured by Murakami Color Research Laboratory) in accordance with JIS K7361-1. The haze value was measured in accordance with JIS K-7136 using a haze meter (HM150, manufactured by Murakami Color Research Laboratory).

[0214] <Residual Solvent Amount in Polyimide Film> After identifying the type of residual solvent in the polyimide film, the content of the identified residual solvent was quantified. [Identifying types of residual solvents] The type of residual solvent was identified using a GC-MS coupled with a purge and trap device (thermal desorption device). A sample tube containing 10 mg of polyimide film was placed in a purge and trap device (product name JTD505-III, Japan Analytical Industry Co., Ltd.) and heated at 200°C for 30 minutes. The generated gas was collected in a trap tube at -60°C, and the collected material was heated at 315°C to remove the gas and sent to a GC-MS for qualitative analysis of the components of the generated organic gas. (Purge & trap device conditions) Total split ratio (intake volume / exhaust volume) 1:10, Carrier gas: Helium 1.0ml / min, constant (GC-MS conditions) Instrument name: GC-MS instrument (Agilent, 6890 / 5973 GC / MS) Column: UA-5, inner diameter 250 μm × length 30 m × film thickness 0.25 μm (manufactured by Frontier Labs), heating conditions: 50°C (hold for 5 minutes) → 10°C / min (heat) → 320°C (hold for 3 minutes) [Quantitative analysis of residual solvents] A polyimide film was added to N,N-dimethylformamide (DMF) so that the concentration of the polyimide film was 5% by mass, and a polyimide film / N,N-dimethylformamide (DMF) solution was prepared. An internal standard solution (0.2% by mass anisole / DMF solution) was added to this solution to prepare a sample solution. The sample solution was subjected to GC-MS measurement under the following conditions using a GC-MS device (e.g., Agilent, 6890 / 5973 GC / MS). The GC-MS measurement was performed three times, and the measurement results were averaged. (GC conditions) Column: InertCapWax inner diameter 250 μm × length 30 m × film thickness 0.25 μm (GL Sciences), Sample injection volume 0.2uL, split ratio 50:1, carrier gas helium 94.3kPa constant pressure, injection port temperature 250℃, heating conditions 40℃ (5 min hold) → 5℃ / min → 120℃ → 20℃ / min → 240℃ (6 min hold), transfer line temperature 250℃ (MS conditions) Ionization method: EI, measurement mode: SIM, ion source temperature: 250°C, quadrupole temperature: 150°C, ionization voltage: 70eV (quantitative ion) DMAc m / z = 72,87 Dichloromethane m / z = 49,84 Cyclopentanone m / z = 55,98

[0215] For example, when the residual solvent is N,N-dimethylacetamide (DMAc), DMAc contents were respectively prepared to be 0.01 mass%, 0.05 mass%, and 0.1 mass% in each DMAc (target compound) / DMF solution, and the internal standard solution was added to each calibration solution in the same manner as in the above-mentioned sample solution. GC-MS measurement was performed to create a calibration curve. The GC-MS measurement was performed three times, and the measurement results were averaged. Then, using the calibration curve as a reference, the DMAc content was calculated as a mass ratio to the polyimide film. When two or more types of residual solvents were contained, a calibration curve solution was prepared for each residual solvent as in the case of DMAc described above, and the calibration curve created from the measurement results of GC-MS measurement for each calibration curve solution was used as the standard.

[0216] <Static bending test (φ2mm, left for 24 hours)> The method of the static bending test will be described below with reference to FIG. A test piece 1 of a polyimide film or laminate cut to 15 mm x 40 mm was folded at the half position of the long side, and both ends of the long side of the test piece 1 were arranged so as to sandwich a metal piece 2 (100 mm x 30 mm x 2 mm) having a thickness of 2 mm from the top and bottom, and fixed with tape so that the overlapping margins of both ends of the test piece 1 and the metal piece 2 on the top and bottom surfaces were 10 mm each. The metal piece 2 to which the test piece 1 was fixed was sandwiched between glass plates (100 mm x 100 mm x 0.7 mm) 3a and 3b from above and below, and the test piece 1 was fixed in a bent state with an inner diameter of 2 mm. At that time, dummy test pieces 4a and 4b were sandwiched in the part of the metal piece 2 where the test piece 1 was not present, and fixed with tape so that the glass plates 3a and 3b were parallel. The test specimen thus fixed in a bent state was left to stand for 24 hours in an environment of room temperature (25°C), 70°C, or 60±2°C and 93±2% relative humidity (RH), or at -40°C, after which the glass plate and the tape used for fixing the test specimen were removed and the force applied to the test specimen was released. One end of the test specimen was then fixed, and the interior angle of the test specimen was measured 30 minutes after the force applied to the test specimen was released. In addition, when the film or laminate is not affected by the static bending test and returns to its original shape completely, the interior angle is 180°.

[0217] <Dynamic bending test (φ2mm)> The method of the dynamic bending test will be described below with reference to FIG. Two movable metal plates 11 (100 mm x 30 mm) each having a movable portion 11a and a non-movable portion 11b were prepared and arranged in parallel such that the distance between the non-movable portions 11b of the two metal plates 11 was 60 mm. The movable portion 11a of the metal plate 11 was bent so as to be perpendicular to the non-movable portion 11b as shown in Fig. 2(A), and a test piece 1 of a polyimide film or laminate cut to 20 mm x 100 mm was placed on the movable portion 11a, and both ends of the test piece 1 were fixed to the movable portion 11a with Kapton (registered trademark) tape so that the center of the test piece 1 was located in the center of the distance between the metal plates. Next, the movable part 11a and the non-movable part 11b were arranged in a straight line to obtain a state as shown in FIG. 2B, that is, the test piece 1 curved at the half position of the long side was sandwiched between the metal plates 11 from both sides, and the metal plates 11 on both sides were arranged in parallel so that the distance between the metal plates 11 on both sides was 60 mm. This state and the state shown in FIG. 2C, in which the metal plates on both sides were arranged in parallel so that the distance between the metal plates 11 on both sides was 2.0 mm, were repeatedly changed at a bending rate of 90 times per minute in an environment of 25° C. and 50% relative humidity (RH) or an environment of 60° C. and 93% relative humidity (RH), and the bending was repeated 200,000 times. A constant temperature and humidity chamber durability test system (Yuasa System Equipment, planar body no-load U-shaped expansion and contraction test jig DMX-FS) was used as the test jig. Thereafter, one end of the test piece was fixed, and the internal angle of the test piece was measured 30 minutes after the force applied to the test piece was released. When the film or laminate is not affected by the dynamic bending test and returns to its original shape completely, the interior angle is 180°. In addition, some test pieces were repeatedly flexed at 90 times per minute in an environment of 60°C and 93% relative humidity (RH) to confirm the number of flexions until breakage. Numbers less than 10,000 are rounded down and shown in the table. (Crack and fracture evaluation criteria) A: No breakage or cracks even after repeated bending 200,000 times. B: Breaks or cracks occur during 200,000 repeated flexions. (Evaluation criteria for the internal angles of the test piece) A: The interior angle is between 140° and 180°. B: The interior angle is greater than or equal to 100° and less than 140°. C: The interior angle is less than 100°.

[0218] <Tensile modulus of polyimide film> A polyimide film test piece cut to 10 mm x 150 mm was conditioned for 2 hours at a temperature of 25°C and a relative humidity of 60%, and then the tensile modulus was measured at 25°C in accordance with JIS K7127 at a pulling speed of 50 mm / min and a chuck distance of 100 mm. The tensile tester used was Shimadzu Corporation's Autograph AG-X 1N, load cell: SBL-1KN.

[0219] <Composite Elastic Modulus> The composite elastic modulus of the polyimide film and the polyimide film in the second laminate was determined as follows. First, the indentation hardness of the polyimide film was measured. IT) was measured on the measurement sample using a "TI950 TriboIndenter" manufactured by BRUKER. Specifically, first, a block was prepared by embedding the polyimide film or the second laminate cut to 1 mm x 10 mm in an embedding resin, and a uniform slice having a thickness of 50 nm to 100 nm without holes was cut from this block by a general slice preparation method. The slice was cut in a direction perpendicular to the plane of the polyimide film. An "Ultramicrotome EM UC7" (manufactured by Leica Microsystems) was used to prepare the slice. The remaining block from which the uniform slice without holes was cut was used as the measurement sample. Next, in the cross section obtained by cutting out the slice in such a measurement sample, a Berkovich indenter (triangular pyramid, TI-0039 manufactured by BRUKER) was pressed vertically into the center of the cross section of the polyimide film for 10 seconds under the following measurement conditions until the maximum pressing load reached 25 μN. At this time, in order to avoid the influence of the glass substrate and the side edges of the polyimide film, the Berkovich indenter was pressed into the interface between the glass substrate and the polyimide film, both side ends of the polyimide film, and into the polyimide film at a distance of 500 nm from the surface of the polyimide film opposite the glass substrate toward the center of the polyimide film. After that, the pressure was held constant to relax the residual stress, and the load was removed over 10 seconds to measure the maximum load after relaxation. max (μN) and contact projection area A p (nm 2 ) and P max / A p The indentation hardness (H IT ) was calculated. The above contact projected area was determined by correcting the indenter tip curvature by the Oliver-Pharr method using a standard sample of fused quartz (5-0098 manufactured by BRUKER). If any of the measured values ​​deviated from the arithmetic mean value by ±20% or more, the measured value was excluded and remeasured.

[0220] (Measurement conditions) ·Loading speed: 2.5μN / sec ·Holding time: 5 seconds ·Loading and unloading speed: 2.5μN / sec ·Measurement temperature: 25℃

[0221] Next, the indentation hardness (H IT ) is measured using the above contact projection area A p The composite elastic modulus was calculated from the above formula (1) using the above formula. The indentation hardness was measured at 10 points, the composite elastic modulus was calculated each time, and the arithmetic average value of the composite elastic moduli obtained at the 10 points was used.

[0222] <Presence or absence of air bubble defects> A total of five polyimide film test pieces cut to 100 mm x 200 mm, that is, a total area of ​​100,000 mm 2 Test pieces were taken so that the area was within 100 mm and visually observed. When the polyimide film was in roll form, test pieces were taken at equal intervals across the entire width of the effective part of the remaining polyimide film roll after trimming and removing the edges, such as the part where the film was gripped for transportation. The polyimide film test pieces were visually observed under fluorescent lights to detect air bubbles. Furthermore, for air bubbles detected by visual observation, the diameter of the air bubbles was measured at 100x magnification using an optical microscope, and air bubbles with a diameter of 0.05 mm or more were counted as air bubble defects. 100,000 mm 2 From the total number of bubbles in the 2 The number of bubbles generated per test was calculated as an average value. In the case of the second laminate in which polyimide is laminated on a glass substrate, the total area of ​​the observed specimens was 100,000 mm 2 The test pieces were taken so that the 2 The number of bubbles generated per test was calculated as an average value. The table shows 20,000 mm 2 The number of bubbles generated per hit was shown.

[0223] <Average thickness, thickness uniformity, appearance> For a polyimide film specimen cut to 100 mm x 200 mm, the length and width of the specimen were regarded as the x-axis and y-axis, and the coordinates of the four corners of the specimen were (0,0), (0,100), (200,0), and (200,100). The film thicknesses of nine points, located at (10,10), (10,50), (10,90), (100,10), (100,50), (100,90), (190,10), (190,50), and (190,90), were measured using a digital linear gauge (Ozaki Manufacturing Co., Ltd., Model PDN12 digital gauge), and the average film thickness measurement value and standard deviation σ were calculated. The appearance was evaluated by checking for waviness and unevenness. When a film had curl and was placed on a platen in a downward convex state, the film was evaluated as having undulations if any part of the film, excluding the four corners, was floating 2 mm or more above the platen. When the film was viewed with transmitted or reflected light, a state in which a streaky pattern was visually confirmed was evaluated as having an uneven appearance. (Evaluation Criteria) A: The film has no waviness or uneven appearance, and the film thickness uniformity is good with 3σ being 2μm or less. B: At least one of the following applies: the film is wavy, has an uneven appearance, and the film thickness uniformity is poor (3σ exceeds 2 μm). In the case of the second laminate in which a polyimide film was laminated on a glass substrate, the film thickness of a test piece of the laminate cut to 100 mm × 200 mm was measured at nine points in total using a digital linear gauge in the same manner as for the polyimide film, and the average value and standard deviation σ of the measured film thickness were calculated. The waviness and unevenness were evaluated in the same manner as for the polyimide film alone. The thickness of the glass substrate and the polyimide film of the laminate was determined from the average thickness of 10 arbitrary locations measured on a cross section of the laminate in the thickness direction observed with a scanning electron microscope.

[0224] (Synthesis Example 1) With reference to Synthesis Example 1 of WO 2014 / 046180, a tetracarboxylic dianhydride represented by the following chemical formula (A) was synthesized.

[0225] [ka]

[0226] A solution of dehydrated N,N-dimethylacetamide (DMAc) (1833.2 g) and 2,2'-bis(trifluoromethyl)benzidine (TFMB) (138.48 g) was placed in a 5L separable flask, and the liquid temperature was controlled at 30°C. Tetracarboxylic dianhydride (TMPBPTME) (176.70 g) represented by the above chemical formula (A) was gradually added so that the temperature rise was 2°C or less, and the mixture was stirred with a mechanical stirrer for 30 minutes. Pyromellitic dianhydride (PMDA) (64.20 g) was gradually added in several portions so that the temperature rise was 2°C or less, synthesizing a polyimide precursor A solution (solid content 18% by mass) in which polyimide precursor A was dissolved. The molar ratio (TMPBPTME:PMDA) of the tetracarboxylic dianhydride TMPBPTME and PMDA used in polyimide precursor A was 90:10. The weight average molecular weight of the polyimide precursor A was 75,000.

[0227] Under a nitrogen atmosphere, the above polyimide precursor A solution (2162 g) was added to a 5 L separable flask, cooled to room temperature. Dehydrated N,N-dimethylacetamide (432 g) was added and stirred until homogenous. Next, catalysts pyridine (6.622 g) and acetic anhydride (213.67 g) were added and stirred at room temperature for 24 hours to synthesize a polyimide A solution. N,N-dimethylacetamide (2000 g) was added to the obtained polyimide A solution and stirred until it became uniform. Next, polyimide solution A was divided into three equal parts and transferred to 5 L beakers, and isopropyl alcohol (3500 g) was gradually added to each beaker to obtain a white slurry. The above slurry was transferred onto a Buchner funnel and filtered, and then washed with isopropyl alcohol (total 9000 g), and the process of filtering was repeated three times, and the mixture was dried at 110 ° C using a vacuum dryer to obtain polyimide A1 (polyimide powder). The weight average molecular weight of Polyimide A1 measured by GPC was 100,000.

[0228] (Synthesis Examples 2 to 6) Polyimides A2 to A6 were prepared in the same manner as in Synthesis Example 1, except that the molar ratio of diamine and acid dianhydride in Synthesis Example 1 was changed. Polyimides A2 to A6 had weight average molecular weights of 123,000, 137,000, 174,000, 235,000, and 266,000, respectively.

[0229] (Synthesis Example 7) A 500mL separable flask was purged with N2, and the solution containing 233.62g of dehydrated dimethylacetamide (DMAc) and 19.22g (60.0mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) was controlled to a liquid temperature of 30°C. 2.34g (11.9mmol) of cyclobutanetetracarboxylic dianhydride (CBDA) and 28.84g (46.6mmol) of TMPBPTME were gradually added so that the temperature rise was 2°C or less, and the mixture was stirred with a mechanical stirrer for 3 hours to obtain a polyamic acid solution. Next, 0.581g (7.3mmol) of pyridine and 18.75g (183.7mol) of acetic anhydride, which are catalysts, were added, and the mixture was stirred at 25°C for 240 minutes to confirm that the solution was homogeneous. After that, 134 g of 2-propyl alcohol (IPA) was gradually added to the solution cooled to room temperature, resulting in a slightly cloudy solution. 223 g of IPA was added to the cloudy solution all at once to obtain a white slurry. The slurry was filtered and washed five times with IPA, and then dried for six hours under reduced pressure in an oven heated to 100°C to obtain a powder of polyimide resin A7 (38.9 g). The weight average molecular weight of the polyimide measured by GPC was 145,000.

[0230] (Synthesis Example 8) A 500 mL separable flask was purged with N2, and 219.23 g of dehydrated dimethylacetamide (DMAc), 16.62 g (51.9 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB), and 0.97 g (2.8 mmol) of diamine represented by the following formula (DA4) (N,N'-bis(4-aminophenyl)terephthalamide, DATA, manufactured by Wakayama Seika Kogyo Co., Ltd.) were dissolved in a solution controlled to a liquid temperature of 30 ° C., and 2.17 g (11.1 mmol) of cyclobutane tetracarboxylic dianhydride (CBDA) and 26.7 g (43.2 mmol) of TMPBPTME were gradually added so that the temperature rise was 2 ° C or less, and the mixture was stirred with a mechanical stirrer for 3 hours to obtain a polyamic acid solution. Next, 0.814g (10.3mmol) of pyridine and 26.274g (257.4mol) of acetic anhydride were added as catalysts, and the mixture was stirred at 25°C for 240 minutes to confirm that the solution was homogeneous. After that, 210g of 2-propyl alcohol (IPA) was gradually added to the solution cooled to room temperature, resulting in a slightly turbid solution. 420g of IPA was added all at once to the turbid solution to obtain a white slurry. The slurry was filtered and washed five times with IPA, and then dried in an oven heated to 100°C under reduced pressure for six hours to obtain a powder of polyimide resin A8 (35.6g). The weight average molecular weight of the polyimide measured by GPC was 183,000.

[0231] [ka]

[0232] (Synthesis Example 9) Polyimide resin A9 was synthesized in the same manner as in Synthesis Example 8, except that in the synthesis of the polyimide resin in Synthesis Example 8, a diamine represented by the following formula (DA33) (4-aminophenyl-4-aminobenzoate, APAB, manufactured by Wakayama Seika Kogyo Co., Ltd.) was used instead of the diamine represented by the formula (DA4) (DATA), and the composition ratio (mol %) of TFMB and APAB was changed as shown in Table 2. The weight average molecular weight of the polyimide measured by GPC was 189,000.

[0233] [ka]

[0234] (Synthesis Example 10) Polyimide resin A10 was synthesized in the same manner as in Synthesis Example 8, except that in the synthesis of the polyimide resin in Synthesis Example 8, a diamine represented by the following formula (DA10) ((2-phenyl-4-aminophenyl)-4-aminobenzoate, PHBAAB, manufactured by Nippon Junryo Chemical Co., Ltd.) was used instead of the diamine represented by the formula (DA4) (DATA), and the composition ratio (mol%) of TFMB and PHBAAB was changed as shown in Table 2. The weight average molecular weight of the polyimide measured by GPC was 160,000.

[0235] [ka]

[0236] (Synthesis Example 11) Polyimide resin A11 was synthesized in the same manner as in Synthesis Example 8, except that in the synthesis of the polyimide resin in Synthesis Example 8, the diamine represented by the formula (DA1) (bis(4-aminophenyl)terephthalate, BPTP: manufactured by Wakayama Seika Kogyo Co., Ltd.) was used instead of the diamine represented by the formula (DA4) (DATA), and the composition ratio (mol%) of TFMB and BPTP was changed as shown in Table 2. The weight average molecular weight of the polyimide measured by GPC was 147,000.

[0237] [ka]

[0238] (Comparative Synthesis Examples 1-2) Comparative polyimide CA1 was prepared in the same manner as in Synthesis Example 1, except that the molar ratio of diamine and acid dianhydride in Synthesis Example 1 was changed. The weight average molecular weight of the comparative polyimide CA1 was 75,000. Comparative polyimide CA2 was prepared in the same manner as in Synthesis Example 1, except that the molar ratio of diamine and acid dianhydride in Synthesis Example 1 was changed. The weight average molecular weight of the comparative polyimide CA2 was 321,000.

[0239] (Comparative Synthesis Example 3) Comparative polyimide CA3 was prepared in the same manner as in the polymerization of the polyimide precursor and the chemical imidization reaction of Example 1 of WO 2014 / 046180. The weight average molecular weight of comparative polyimide CA3 was 288,000.

[0240] Example 1 Polyimide films having the thicknesses shown in Table 1 were produced by using Polyimide A1 of Synthesis Example 1 and carrying out the procedures (P1) to (P3) below. (P1) A mixed solvent of dichloromethane (DCM) and methanol (dichloromethane:methanol = 98:2 (mass ratio)) was added to polyimide A1 so that the solid content concentration of polyimide A1 was 10 mass %, to prepare polyimide A1 varnish with a polyimide content of 10 mass % in the varnish. The viscosity of polyimide A1 varnish (solid content concentration 10 mass %) at 25 ° C. was 1200 cps. (P2) Polyimide A1 varnish (solid content concentration 10% by mass) was applied to a sheet-like support (thickness 100 μm, SUS304, manufactured by Nisshin Steel Co., Ltd., SUS304 CSP-H-TA) so that the film thickness after drying in a circulation oven described below would be the thickness shown in Table 1. The varnish applied to the support was left to stand at 25° C. for 30 minutes in a dichloromethane atmosphere in a glove bag to dry, and then the atmosphere in the glove bag was replaced with an air atmosphere and left to stand at 25° C. for 5 minutes to dry. The support and the dried coating film were removed from the glove bag, and the dried coating film was peeled off from the support. (P3) The peeled dried coating film was cut into a size of 150 mm x 200 mm. The cut dried coating film was sandwiched between two metal frames (outer dimensions 150 mm x 200 mm, inner dimensions 130 mm x 180 mm), and the metal frames and dried coating film were fixed with a fixing jig. The fixed dried coating film was heated in a circulation oven at a temperature increase rate of 5°C / min, and dried at 140°C for 2 minutes, 170°C for 2 minutes, and 200°C for 10 minutes to produce a polyimide film. The evaluation results of the obtained polyimide film are shown in Table 1.

[0241] (Examples 2 to 11, 13 to 17, Comparative Examples 1 to 3) Polyimide varnishes were prepared in the same manner as in Example 1, except that in step (P1) of Example 1, the polyimide and the polyimide concentration (mass %) in the varnish were changed as shown in Table 1. Polyimide films were produced in the same manner as in steps (P2) and (P3) of Example 1 using each polyimide varnish. The evaluation results of the obtained polyimide film are shown in Tables 1 and 2.

[0242] Example 12 A polyimide film having a thickness as shown in Table 2 was produced by using Polyimide A4 of Synthesis Example 4 and carrying out the procedures (P1') to (P3') below. (P1') Polyimide A4' varnish was prepared by adding DMAc to polyimide A4 so that the solid content of polyimide A4 was 10% by mass. The viscosity of polyimide A4' varnish (solid content concentration 10% by mass) at 25°C was 7400 cps. (P2') The polyimide A4' varnish (solid content concentration 10% by mass) was applied to a sheet-like support (thickness 100 μm, SUS304, manufactured by Nisshin Steel Co., Ltd., SUS304 CSP-H-TA) so that the film thickness after drying in a circulation oven described below would be the thickness shown in Table 2. The varnish applied to the support was heated from 25° C. to 80° C. over 10 minutes, dried at 80° C. for 30 minutes and then at 100° C. for 30 minutes, and the coating film was peeled off from the support. (P3') The peeled dried coating film was cut into a size of 150 mm x 200 mm. The cut dried coating film was sandwiched between two metal frames (outer dimensions 150 mm x 200 mm, inner dimensions 130 mm x 180 mm), and the metal frames and dried coating film were fixed with a fixing jig. The fixed dried coating film was heated in a circulation oven at a temperature increase rate of 5°C / min, and dried at 150°C for 10 minutes, 180°C for 10 minutes, 230°C for 10 minutes, and 250°C for 30 minutes to produce a polyimide film. The evaluation results of the obtained polyimide film are shown in Table 2.

[0243] Comparative Example 4 Using the comparative polyimide CA3 obtained in Comparative Synthesis Example 3, a polyimide film was produced in the same manner as in the preparation of a polyimide solution and the production of a polyimide film in Example 1 of WO2014 / 046180. The evaluation results of the obtained polyimide film are shown in Table 2. In the table, "no data" means that no measurement was performed.

[0244] [Table 1]

[0245] [Table 2]

[0246] The polyimide films of Comparative Examples 3 and 4 were both broken at air bubble defects in a dynamic bending test at 60° C. and 93% relative humidity.

[0247] (Example 18: Production of a second laminate) (1) Preparation of glass substrate A chemically strengthened glass substrate (UTG) having a thickness of 30 μm was prepared, and the primer layer composition described below was applied to the glass substrate to a predetermined thickness, and dried at 80°C for 3 minutes and at 150°C for 60 minutes to form a primer layer having a thickness of 1 μm. (Primer layer composition) Bisphenol A type solid epoxy resin (jER1256B40, manufactured by Mitsubishi Chemical) 28 parts by weight Bisphenol A novolac type solid epoxy resin (jER157S65B80, manufactured by Mitsubishi Chemical) 5 parts by weight 2-Ethyl-4-methylimidazole (Tokyo Chemical Industry Co., Ltd.) 1 part by weight Solvent (MEK) 11 parts by weight

[0248] (2) Lamination of polyimide film Using the polyimide A1 of Synthesis Example 1, the following procedures (L1) to (L3) were carried out to produce polyimide films having thicknesses shown in Table 3 on the primer layer formed on the glass substrate, thereby producing a second laminate. (L1) A mixed solvent of dichloromethane and methanol (dichloromethane:methanol=98:2 (mass ratio)) was added to polyimide A1 so that the solid content concentration of polyimide A1 was 10 mass %, to prepare polyimide A1 varnish containing 10 mass % of polyimide in the varnish. The viscosity of polyimide A1 varnish (solid content concentration 10 mass %) at 25°C was 1200 cps. (L2) Polyimide A1 varnish (solid content concentration 10% by mass) was applied onto the primer layer formed on the glass substrate so that the film thickness after drying in a circulation oven described below would be the thickness shown in Table 3. The applied varnish was left to stand at 25°C for 30 minutes in a dichloromethane atmosphere in a glove bag to dry, and then the atmosphere in the glove bag was replaced with an air atmosphere and left to stand at 25°C for 5 minutes to dry. The glass substrate and the dried coating film were removed from the glove bag. (L3) The glass substrate and the dried coating film were heated in a circulating oven at a heating rate of 5°C / min, and dried at 140°C for 2 minutes, at 170°C for 2 minutes, and at 200°C for 10 minutes to produce a second laminate in which a polyimide film was laminated on the glass substrate. The evaluation results of the obtained second laminate are shown in Table 3.

[0249] (Examples 19 to 28, 30 to 34, Comparative Examples 5 to 7) A polyimide varnish was prepared in the same manner as in Example 18, except that in step (L1) of Example 18, the polyimide and the polyimide concentration (mass%) in the varnish were changed as shown in Tables 3 and 4. Using each polyimide varnish, a second laminate in which a polyimide film was laminated on the glass substrate was produced in the same manner as in steps (L2) and (L3) of Example 18. The evaluation results of the obtained second laminate are shown in Tables 3 and 4.

[0250] (Example 29) In Example 18, (2) Lamination of polyimide film, a second laminate was produced in the same manner as in Example 18, except that polyimide A4 of Synthesis Example 4 was used and a polyimide film having a thickness shown in Table 4 was produced by carrying out the steps (L1') to (L3') below. (L1') Polyimide A4' varnish was prepared by adding DMAc to polyimide A4 so that the solid content of polyimide A4 was 10% by mass. The viscosity of polyimide A4' varnish (solid content concentration 10% by mass) at 25°C was 7400 cps. (L2') Onto the primer layer formed on the glass substrate, the polyimide A4' varnish (solid content concentration: 10% by mass) was applied so that the film thickness after drying in a circulating oven described below would be the thickness shown in Table 4. The applied varnish was heated from 25°C to 80°C over 10 minutes, and dried at 80°C for 30 minutes and then at 100°C for 30 minutes. (L3') The glass substrate and the dried coating film were heated in a circulating oven at a heating rate of 5°C / min, and dried at 150°C for 10 minutes, 180°C for 10 minutes, 230°C for 10 minutes, and 250°C for 30 minutes to produce a second laminate in which a polyimide film was laminated to the glass substrate. The evaluation results of the obtained second laminate are shown in Table 4.

[0251] Comparative Example 8 A polyimide solution was prepared in the same manner as in Example 1 of WO 2014 / 046180 using the comparative polyimide CA3 obtained in Comparative Synthesis Example 3, and a polyimide film was laminated on the glass substrate in the same manner as in the production of the polyimide film in Example 1 of WO 2014 / 046180, except that the same glass substrate as in Example 18 (a primer layer laminated on a 30 μm-thick chemically strengthened glass substrate (UTG)) was used as the glass substrate, and the polyimide film was not peeled off from the glass substrate.

[0252] [Table 3]

[0253] [Table 4]

[0254] It was shown that the second laminate of the present invention is less susceptible to bubble defects, has good film thickness uniformity, and has good bending resistance. In addition, when comparing the composite modulus of elasticity of Example 6 with that of Example 23, and that of Examples 12 to 17 with that of Examples 29 to 34, it was shown that even if the same polyimide was used, the composite modulus of elasticity of the polyimide film laminated on the glass substrate was higher than that of the polyimide film alone. In other words, it was shown that even if the same polyimide was used, the polyimide film laminated on the glass substrate could obtain a higher surface hardness. It is considered that the defects such as the fragility and insufficient impact resistance of the glass substrate can be complemented by laminating a resin layer on a glass substrate having a thickness of 100 μm or less, but the surface hardness is significantly reduced depending on the resin layer. In contrast, it was shown that the second laminate laminated with the polyimide film of the present invention can obtain a high surface hardness by a synergistic effect while complementing the defects of the glass substrate having a thickness of 100 μm or less.

[0255] (Examples 35 to 51: Production of first laminate) A resin composition for a hard coat layer was prepared by adding 10 parts by mass of 1-hydroxycyclohexylphenylketone (Irgacure 184, manufactured by BASF) to 100 parts by mass of pentaerythritol triacrylate in a 40% by mass methyl isobutyl ketone solution of pentaerythritol triacrylate. The resin composition for hard coat layer was applied onto each of the polyimide films of Examples 1 to 17, and ultraviolet rays were irradiated at 200 mJ / cm under a nitrogen gas flow. 2 The coating was cured by exposure to an exposure dose of 10 μm to form a cured film having a thickness of 10 μm, thereby producing a first laminate.

Claims

1. The polyimide film contains a polyimide having a weight average molecular weight of 100,000 or more and 270,000 or less as calculated on a polystyrene basis by gel permeation chromatography, the weight average molecular weight being 100,000 or more and 270,000 or less, and the polyimide film contains 1 ppm or more and 2000 ppm or less of dichloromethane. The weight average molecular weight is determined by gel permeation chromatography using a polystyrene equivalent. The weight average molecular weight is determined by a polystyrene equivalent basis and the weight average molecular weight is 100,000 or more and 270,000 or less, and the polyimide film contains 1 ppm or more and 2000 ppm or less of dichloromethane. 【Chemistry 1】 (In general formulas (1) and (2), R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 1 and R 2 At least one of, and R 3 and R 4 At least one of A represents an alkyl group having 1 to 6 carbon atoms, A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring.

2. A polyimide film as described in claim 1, having a content of organic solvents having a boiling point of 100°C or higher at 1 atmosphere of 100 ppm or less.

3. The diamine residue having an aromatic ring or an aliphatic ring in B in the general formulas (1) and (2) is a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, a 3,3'-bis(trifluoromethyl)-4,4'-[(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)bis(4,1-phenyleneoxy)]dianiline residue, a 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3, The polyimide film according to claim 1 or 2, which is a divalent group containing at least one selected from the group consisting of 3,3-hexafluoropropane residues, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane residues, and divalent groups represented by the following general formula (3), and which may further contain at least one selected from the group consisting of N,N'-bis(4-aminophenyl)terephthalamide residues, 4-aminophenyl-4-aminobenzoate residues, (2-phenyl-4-aminophenyl)-4-aminobenzoate residues, and bis(4-aminophenyl)terephthalate residues. 【Chemistry 2】 (In the general formula (3), R 5 and R 6 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.

4. The tetracarboxylic acid residue having an aromatic ring or an aliphatic ring in A in the general formula (2) is a cyclohexanetetracarboxylic acid dianhydride residue, a cyclopentanetetracarboxylic acid dianhydride residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid dianhydride residue, a cyclobutanetetracarboxylic acid dianhydride residue, a pyromellitic acid dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic acid dianhydride residue, a 2,2',3,3'-biphenyltetracarboxylic acid dianhydride residue, a 2 ...

4. The polyimide film according to claim 1, wherein the tetravalent group is at least one selected from the group consisting of a 4,4'-biphenyltetracarboxylic dianhydride residue, a 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 3,3'-(hexafluoroisopropylidene)diphthalic anhydride residue, a 4,4'-oxydiphthalic anhydride residue, and a 3,4'-oxydiphthalic anhydride residue.

5. A polyimide varnish containing a polyimide and an organic solvent, The polyimide contains 10 mol % or more and 100 mol % or less of a constitutional unit represented by the following general formula (1) and (100-x) mol % (wherein x is the mol % of the constitutional unit represented by the general formula (1)) of a constitutional unit represented by the following general formula (2), and has a weight average molecular weight of 100,000 or more and 270,000 or less as calculated in terms of polystyrene by gel permeation chromatography: The organic solvent contains dichloromethane in an amount of 90% by mass or more based on the total amount of the organic solvent. The polyimide varnish has a content of the polyimide in the polyimide varnish of 6% by mass or more and 15% by mass or less. 【Chemistry 3】 (In general formulas (1) and (2), R 1 ~R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 1 and R 2 At least one of, and R 3 and R 4 At least one of A represents an alkyl group having 1 to 6 carbon atoms, A represents a tetravalent group which is a tetracarboxylic acid residue having an aromatic ring or an aliphatic ring, and B represents a divalent group which is a diamine residue having an aromatic ring or an aliphatic ring.

6. The polyimide varnish described in claim 5, wherein the polyimide has a content of organic solvents having a boiling point of 100°C or higher at 1 atmosphere of 100 ppm or less.

7. The diamine residue having an aromatic ring or an aliphatic ring in B in the general formulas (1) and (2) is a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenylsulfone residue, a 3,4'-diaminodiphenylsulfone residue, a 2,2-bis(4-aminophenyl)propane residue, a 3,3'-bis(trifluoromethyl)-4,4'-[(1,1,1,3,3,3-hexafluoropropane-2,2-diyl)bis(4,1-phenyleneoxy)]dianiline residue, a 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3, The polyimide varnish according to claim 5 or 6, which is a divalent group containing at least one selected from the group consisting of 3,3-hexafluoropropane residues, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane residues, and divalent groups represented by the following general formula (3), and which may further contain at least one selected from the group consisting of N,N'-bis(4-aminophenyl)terephthalamide residues, 4-aminophenyl-4-aminobenzoate residues, (2-phenyl-4-aminophenyl)-4-aminobenzoate residues, and bis(4-aminophenyl)terephthalate residues. 【Chemistry 4】 (In the general formula (3), R 5 and R 6 each independently represents a hydrogen atom, an alkyl group, or a perfluoroalkyl group.

8. The tetracarboxylic acid residue having an aromatic ring or an aliphatic ring in A in the general formula (2) is a cyclohexanetetracarboxylic acid dianhydride residue, a cyclopentanetetracarboxylic acid dianhydride residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid dianhydride residue, a cyclobutanetetracarboxylic acid dianhydride residue, a pyromellitic acid dianhydride residue, a 3,3',4,4'-biphenyltetracarboxylic acid dianhydride residue, a 2,2',3,3'-biphenyltetracarboxylic acid dianhydride residue, a 2,3, The polyimide varnish according to any one of claims 5 to 7, which is at least one tetravalent group selected from the group consisting of 3',4'-biphenyltetracarboxylic dianhydride residues, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, 3,4'-(hexafluoroisopropylidene)diphthalic anhydride residues, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride residues, 4,4'-oxydiphthalic anhydride residues, and 3,4'-oxydiphthalic anhydride residues.

9. A step of preparing the polyimide varnish according to any one of claims 5 to 8, the polyimide varnish having a viscosity of 1,000 to 10,000 cps at 25°C as measured by a rotational viscometer; applying the polyimide varnish to a support, drying the polyimide varnish at a temperature of 40° C. or less, and peeling the coating film from the support after drying; A method for producing a polyimide film, comprising the steps of fixing an end portion of the dried coating film peeled off from the support, and then heating the dried coating film at a temperature of 150° C. or higher.

10. A method for producing a polyimide film as described in claim 9, comprising a step of fixing the ends of the dried coating film peeled off from the support, and then heating the dried coating film by gradually increasing the temperature from room temperature to a maximum temperature of 150°C or higher.

11. A laminate comprising the polyimide film according to claim 1 and a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound.

12. A laminate comprising a glass substrate having a thickness of 100 μm or less and the polyimide film according to claim 1 .

13. 5. A laminate comprising, in this order: a glass substrate having a thickness of 100 μm or less; the polyimide film according to claim 1 ; and a hard coat layer containing at least one polymer of a radically polymerizable compound and a cationic polymerizable compound.

14. A display member comprising the polyimide film according to any one of claims 1 to 4 or the laminate according to any one of claims 11 to 13.

15. The polyimide film according to any one of claims 1 to 4 or the laminate according to any one of claims 11 to 13, a transparent electrode including a plurality of conductive portions disposed on one surface side of the polyimide film or the laminate; and a plurality of lead wires electrically connected to at least one side of an end of the conductive portion.

16. The polyimide film according to any one of claims 1 to 4 or the laminate according to any one of claims 11 to 13, a liquid crystal display section disposed on one surface side of the polyimide film or the laminate and having a liquid crystal layer between opposing substrates;

17. The polyimide film according to any one of claims 1 to 4 or the laminate according to any one of claims 11 to 13, an organic electroluminescence display unit having an organic electroluminescence layer between opposing substrates, the organic electroluminescence display unit being disposed on one surface side of the polyimide film or the laminate;

Citation Information

Patent Citations

  • Low water absorbable polyimide resin and process for its production

    JP2006199945A

  • Transparent substrate

    JP2011088789A

  • Transparent polyimide film and method for manufacturing the same

    JP2014501301A

  • Laminate for touch panel and folding type picture display unit

    JP2017033035A

  • Polyimide resin

    WO2008010494A1